3D real-time echocardiography combined with mini pressure wire generate reliable pressure-volume loops in small hearts - Herberg, Ulrike; Linden, Katharina; Dewald, Oliver; Gatzweiler, Eva; Seehase, Matthias; Duerr, Georg Daniel; Doerner, Jonas; Kleppe, Stephanie; Ladage, Dennis; Breuer, Johannes (PLoS ONE, 2016)
Background: Pressure-volume loops (PVL) provide vital information regarding ventricular performance and pathophysiology in cardiac disease. Unfortunately, acquisition of PVL by conductance technology is not feasible in neonates and small children due to the available human catheter size and resulting invasiveness. The aim of the study was to validate the accuracy of PVL in small hearts using volume data obtained by real-time three-dimensional echocardiography (3DE) and simultaneously acquired pressure data. Methods: In 17 piglets (weight range: 3.6-8.0 kg) left ventricular PVL were generated by 3DE and simultaneous recordings of ventricular pressure using a mini pressure wire (PVL3D). PVL3Dwere compared to conductance catheter measurements (PVLCond) under various hemodynamic conditions (baseline, alpha-adrenergic stimulation with phenylephrine, beta-adrenoreceptorblockage using esmolol). In order to validate the accuracy of 3D volumetric data, cardiac magnetic resonance imaging (CMR) was performed in another 8 piglets. Results: Correlation between CMR- and 3DE-derived volumes was good (enddiastolic volume: mean bias -0.03ml ±1.34ml). Computation of PVL3Din small hearts was feasible and comparable to results obtained by conductance technology. Bland-Altman analysis showed a low bias between PVL3Dand PVLCond. Systolic and diastolic parameters were closely associated (Intraclass-Correlation Coefficient for: systolic myocardial elastance 0.95, arterial elastance 0.93, diastolic relaxation constant tau 0.90, indexed end-diastolic volume 0.98). Hemodynamic changes under different conditions were well detected by both methods (ICC 0.82 to 0.98). Inter- and intra-observer coefficients of variation were below 5% for all parameters. Conclusions: PVL3Dgenerated from 3DE combined with mini pressure wire represent a novel, feasible and reliable method to assess different hemodynamic conditions of cardiac function in hearts comparable to neonate and infant size. This methodology may be integrated into clinical practice and cardiac catheterization programs and has the capability to contribute to clinical decision making even in small hearts.
CRIS-Team Scopus Importer:2022-05-03

Activation of Endocannabinoid System Is Associated with Persistent Inflammation in Human Aortic Aneurysm - Gestrich, Christopher; Duerr, Georg D.; Heinemann, Jan C.; Meertz, Anne; Probst, Chris; Roell, Wilhelm; Schiller, Wolfgang; Zimmer, Andreas; Bindila, Laura; Lutz, Beat; Welz, Armin; Dewald, Oliver (BioMed Research International, 2015)
Human aortic aneurysms have been associated with inflammation and vascular remodeling. Since the endocannabinoid system modulates inflammation and tissue remodeling, we investigated its components in human aortic aneurysms. We obtained anterior aortic wall samples from patients undergoing elective surgery for aortic aneurysm or coronary artery disease as controls. Histological and molecular analysis (RT-qPCR) was performed, and endocannabinoid concentration was determined using LC-MRM. Patient characteristics were comparable between the groups except for a higher incidence of arterial hypertension and diabetes in the control group. mRNA level of cannabinoid receptors was significantly higher in aneurysms than in controls. Concentration of the endocannabinoid 2-arachidonoylglycerol was significantly higher, while the second endocannabinoid anandamide and its metabolite arachidonic acid and palmitoylethanolamide were significantly lower in aneurysms. Histology revealed persistent infiltration of newly recruited leukocytes and significantly higher mononuclear cell density in adventitia of the aneurysms. Proinflammatory environment in aneurysms was shown by significant upregulation of M-CSF and PPARγ but associated with downregulation of chemokines. We found comparable collagen-stained area between the groups, significantly decreased mRNA level of CTGF, osteopontin-1, and MMP-2, and increased TIMP-4 expression in aneurysms. Our data provides evidence for endocannabinoid system activation in human aortic aneurysms, associated with persistent low-level inflammation and vascular remodeling.
CRIS-Team Scopus Importer:2022-05-03

A Half-Century of Heterotopic Heart Transplantation in Mice: The Spearhead of Immunology Research - Yin, Decheng; Dewald, Oliver; Peng, Xiangyu; Nie, Wenlong; Rong, Song; Dudziak, Diana; Lehmann, Christian; Hörning, André; Fu, Jian (Transplantology, 2024)
Since the success of solid organ transplants, such as human kidneys, livers and hearts, from the 50s to the 60s in the last century, the field of organ transplantation has progressed rapidly. Mainly due to modifications in surgical operation techniques and improvements in immunosuppressive therapy regimes, organ survival time can now be greatly prolonged. This progress has also been dependent upon the availability of appropriate animal models for organ transplantation. Therefore, the mouse heart transplantation model has developed into an irreplaceable research model for solid organ transplantation, providing indelible contributions to the field. In this review, we will provide an overview of the technical developments in murine heart transplantation, as well as its historical and current role for alloimmune research. Further, we will describe its current fields of application and its scientific achievements before we discuss potential future applications.
CRIS-Team Scopus Importer:2025-02-04
Keywords: heterotopic heart transplantation; immunology; murine transplantation

Anaesthesiological managemnet at paediatric cardiac surgical centres in Germany: Current status of personnel and structural organisation Anästhesiologische Versorgung an deutschen Zentren für Kinderherzchirurgie: Aktueller Stand der personellen und strukturellen Organisation - Bähner, T.; Heinze, I.; Mueller, M.; Schindler, E.; Schirmer, U.; Hoeft, A.; Baumgarten, G.; Ellerkmann, R. K.; Dewald, Oliver (Anästhesiologie & Intensivmedizin, 2016)
Background: Owing to its complexity paediatric cardiac anaesthesia requires a high level of expert knowledge. There are currently no recommendations for standards in paediatric cardiac anaesthesia in Germany. The aim of the present study was to assess the current structural and personnel anaesthetic standards in paediatric cardiac surgical centres in Germany. Method: The participating centres were interviewed using an online questionnaire to assess current practice in paediatric cardiac anaesthesia. The questionnaire contained 55 items subdivided in 16 categories on 30 pages. Results: An active programme for congenital heart surgery was identified in 27 hospitals in Germany. The questionnaire response rate was 96.3%. A specialised group of anaesthesiologists concerned with paediatric cardiac anaesthesia was reported to exist by 92.3% of participating centres, with a mean size of 4.8 anaesthesiologists per group in each centre. However, the annual case load of each anaesthesiologist varies considerably. Currently, only 26.9% of the centres ensure an intraoperative management by two anaesthesiologists per patient. An additional supervisor is present in 53.8% of the centres. Sedation and general anaesthesia for diagnostic and therapeutic interventions outside the operating theatre in patients with congenital heart disease is also performed by non-anaesthesiologists in 76.9% of the centres. Special equipment, e.g. mechanical autotransfusion, ultrasound for vascular access, transoesophageal echocardiography and near-infrared spectroscopy is mostly available but not often routinely used. Conclusion: This study presents the current structural and personnel standards for paediatric cardiac anaesthesia at the centres for congenital heart surgery in Germany.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Congenital Heart Disease; Congenital Heart Surgery; Paediatric Cardiac Anaesthesia

Application comparison of paediatric myocardial protection procedures in arterial switch surgery - Münch, Frank; Kohl, Matthias; Kwapil, Nicola; Dewald, Oliver; Cuomo, Michela; Purbojo, Ariawan (Perfusion-Uk, 2024)
Background: Reliable myocardial protection is essential for a good outcome after arterial switch operation. Patients and Methods: We evaluated 56 neonates with arterial switch operation in this retrospective study. Three types of cardioplegia were used: antegrade Custodiol® (CCC) n = 22, antegrade Custodiol® plus paediatric microplegia (mix) n = 14, and antegrade plus retrograde intermittently paediatric microplegia (blood) n = 20. We evaluated the extent of myocardial injury using troponin I, Creatine kinase (CK), CK-MB (CK in myocardial cells) and vasoactive inotrope score (VIS), immediately- and the first postoperative day, as well as outcome parameters. A statistical analysis was conducted using multiple linear regression, with adjustments made for the RACHS score and ischemia time, at a significance level of 5%. Results: Preoperative data were comparable between the three groups. Aortic cross clamp time was significantly different between the three groups (CCC: 115 ± 26 min: mix: 162 ± 35 min: blood: 153 ± 31 min). We found significantly lower troponin I release in the blood group 14 ng/mL [CI95 10; 18] versus CCC group 36 ng/mL [CI95 27; 48] and versus mix group 27 ng/mL [CI95 19; 38]; troponin I 24 h blood group 8 ng/mL [CI95 6; 11] versus CCC group 14 ng/mL [CI95 10; 19]. No significant differences were found in CK, CK-MB, VIS, as well as in outcome parameters 30-day mortality, ventilation time, hospital stay or ECMO implantation. Conclusions: Intermittent paediatric microplegia led to a significantly lower release of troponin I, despite significantly longer ischemia times than after application of Custodiol®. Paediatric microplegia can be safely performed in neonates and also offers the advantage of miniaturization of the Cardiopulmonary bypass setup.
CRIS-Team Scopus Importer:2025-02-04
Keywords: arterial switch operation; cardioplegia; cardiopulmonary bypass (CPB); microplegia; myocardial protection; paediatric

A role for 12/15-lipoxygenase-derived proresolving mediators in postoperative ileus: protectin DX-regulated neutrophil extravasation - Stein, Kathy; Stoffels, Melissa; Lysson, Mariola; Schneiker, Bianca; Dewald, Oliver; Krönke, Gerhard; Kalff, Joerg C.; Wehner, Sven (Journal of Leukocyte Biology, 2016)
Resolution of inflammation is an active counter-regulatory mechanism involving polyunsaturated fatty acid-derived proresolving lipid mediators. Postoperative intestinal motility disturbances, clinically known as postoperative ileus, occur frequently after abdominal surgery and are mediated by a complex inflammation of the intestinal muscularis externa. Herein, we tested the hypothesis that proresolving lipid mediators are involved in the resolution of postoperative ileus. In a standardized experimental model of postoperative ileus, we detected strong expression of 12/15-lipoxygenase within the postoperative muscularis externa of C57BL/6 mice, predominately located within CX3CR1(+)/Ly6C(+) infiltrating monocytes rather than Ly6G(+) neutrophils. Mass spectrometry analyses demonstrated that a 12/15-lipoxygenase increase was accompanied by production of docosahexaenoic acid-derived lipid mediators, particularly protectin DX and resolvin D2, and their common precursor 17-hydroxy docosahexaenoic acid. Perioperative administration of protectin DX, but not resolvin D2 diminished blood-derived leukocyte infiltration into the surgically manipulated muscularis externa and improved the gastrointestinal motility. Flow cytometry analyses showed impaired Ly6G(+)/Ly6C(+) neutrophil extravasation after protectin DX treatment, whereas Ly6G(-)/Ly6C(+) monocyte numbers were not affected. 12/15-lipoxygenase-deficient mice, lacking endogenous protectin DX synthesis, demonstrated increased postoperative leukocyte levels. Preoperative intravenous administration of a docosahexaenoic acid-rich lipid emulsion reduced postoperative leukocyte infiltration in wild-type mice but failed in 12/15-lipoxygenase-deficient mice mice. Protectin DX application reduced leukocyte influx and rescued 12/15-lipoxygenase-deficient mice mice from postoperative ileus. In conclusion, our results show that 12/15-lipoxygenase mediates postoperative ileus resolution via production of proresolving docosahexaenoic acid-derived protectin DX. Perioperative, parenteral protectin DX or docosahexaenoic acid supplementation, as well as modulation of the 12/15-lipoxygenase pathway, may be instrumental in prevention of postoperative ileus.
EVALuna2:13152

Automatic Segmentation of Lymphatic Perfusion in Patients with Congenital Single Ventricle Defects - Stegmaier, Marietta; Schröder, Christian; Müller, Johanna; Day, Thomas; Cuomo, Michela; Dewald, Oliver; Dittrich, Sven; Kainz, Bernhard (Bildverarbeitung für die Medizin 2024. BVM 2024, 2024)
The Fontan circulation is the surgical end-point for a variety of singleventricle congenital heart lesions. While recent decades have witnessed substantial improvements in survival rates, the associated physiology remains susceptible to severe complications such as protein-losing enteropathy and plastic bronchitis. These complications are often indicative of abnormal congestion in the lymphatic system, underscoring their significance as harbingers of impending comorbidities. An accurate assessment of congestion severity requires the detailed annotation of lymphatic perfusion patterns in each volumetric scan slice. The manual labelling of such intricate data is time-consuming and demands a high level of expertise, rendering it unfeasible within the confines of standard clinical protocols. We use a curated database consisting of manually annotated T2-weighted magnetic resonance imaging (MRI) scans from 71 Fontan patients post-surgery. Following the current state-of-the-art method for biomedical image segmentation, we evaluate its performance on multiple independent test sets regarding the degree of severity and imaging quality. Incorporating the best-performing model,we have developed a user-friendly interface for the automatic segmentation of lymphatic malformations, which will be published before the conference starts.
CRIS-Team Scopus Importer:2024-03-29

Calcified Amorphous Tumor and Granulomatosis with Polyangiitis—Case Report and Systematic Review of the Literature - Suleiman, Mathieu; Agaimy, Abbas; Dewald, Oliver; Kaemmerer-Suleiman, Ann-Sophie; Mellert, Fritz; Weyand, Michael; Harig, Frank (Journal of Clinical Medicine, 2025)
Background: Calcified amorphous tumor (CAT) is a rare, mostly incidental tumor-like cardiac lesion of unknown histogenesis. Current imaging modalities do not differentiate between CAT and other masses. As it can be a source for embolization, surgical excision of CAT is mandatory. CAT in patients with Granulomatosis with polyangiitis (GPA) is exceedingly rare. Methods: This systematic literature review was prompted by the case of a CAT in a patient with GPA. The search of all types of studies in two databases (PubMed and Scopus) was conducted through November 2024 to identify the relevant studies. Results: Nine studies were included describing cases of patients being diagnosed with GPA and a cardiac mass. All included patients had a histopathological examination of the either biopsied or surgically resected mass. Only one case reported a CAT. In our case, the patient was diagnosed with GPA through a kidney biopsy, whereas a cardiac mass in the right atrium was diagnosed by echocardiography during evaluation for possible kidney transplantation. One year later a progression was observed, and the mass was resected. The histopathological examination revealed a CAT. The patient could be successfully discharged in a good clinical condition. Conclusions: This systematic literature search and case report highlight the importance of regular echocardiographic examination in patients with GPA. Moreover, surgical excision is crucial for the diagnosis and for further therapy planning, regardless of whether the mass is neoplastic or not.
CRIS-Team Scopus Importer:2025-01-31
Keywords: calcified amorphous tumors; cardiac mass; CAT; granulomatosis with polyangiitis (GPA); Wegener’s granulomatosis

Cardiomyocyte specific peroxisome proliferator-activated receptor-α overexpression leads to irreversible damage in ischemic murine heart - Duerr, Georg D.; Heinemann, Jan C.; Arnoldi, Vanessa; Feisst, Andreas; Kley, Julian; Ghanem, Alexander; Welz, Armin; Dewald, Oliver (Life Sciences, 2014)
Aims Peroxisome proliferator-activated receptor (PPAR)-α is downregulated in ischemic myocardium resulting in substrate switch from fatty acid oxidation to glucose utilization. Pharmacological PPAR-α activation leads to increased fatty acid oxidation and myocardial lipotoxicity. The aim of our study was to investigate the role of cardiomyocyte specific PPAR-α overexpression in myocardial adaptation to repetitive ischemic injury without myocardial infarction. Main methods Repetitive, brief I/R was performed in male and female MHC-PPAR-α overexpressing and wildtype-C57/Bl6 (WT)-mice, age 10-12 weeks, for 3 and 7 consecutive days. After echocardiography, their hearts were excised for histology and gene/protein-expression measurements (Taqman/Western blot). Key findings MHC-PPAR-α mice developed microinfarctions already after 3 days of repetitive I/R in contrast to interstitial fibrosis in WT-mice. We found higher deposition of glycogen, increased apoptosis and dysfunctional regulation of antioxidative mediators in MHC-PPAR-α mice. MHC-PPAR-α mice presented with maladaptation of myosin heavy chain isoforms and worse left ventricular dysfunction than WT-mice. We found prolonged, chemokine-driven macrophage infiltration without induction of proinflammatory cytokines in MHC-PPAR-α mice. Persistent accumulation of myofibroblasts in microinfarctions indicated active remodeling resulting in scar formation in contrast to interstitial fibrosis without microinfarctions in WT-mice. However, MHC-PPAR-α hearts had only a weak induction of tenascin-C in contrast to its strong expression in WT-hearts. Significance Cardiomyocyte-specific PPAR-α overexpression led to irreversible cardiomyocyte loss with deteriorated ventricular function during brief, repetitive I/R episodes. We identified higher glycogen deposition, increased apoptosis, deranged antioxidative capacity and maladaptation of contractile elements as major contributors involved in the modulation of post-ischemic inflammation and remodeling. © 2014 Elsevier Inc.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Apoptosis; Chemokines; Diabetes; Inflammation; Ischemia/reperfusion; PPAR-α; Remodeling

Cardiomyoplasty improves contractile reserve after myocardial injury in mice: Functional and morphological investigations with reconstructive three-dimensional echocardiography - Ghanem, Alexander; Roell, Wilhelm; Bostani, Toktam; Dewald, Oliver; Fleischmann, Bernd K.; Stypmann, Joerg; Nickenig, Georg; Tiemann, Klaus (Cell Transplantation, 2011)
Cellular cardiomyoplasty (CMP) is a novel therapeutic approach to myocardial injury (MI). Post-MI remodeling of the left ventricle (LV) comprises dilatation and impairment of systolic function and gives rise to progressive hemodynamic deterioration. We aimed to investigate: a) the impact of CMP on global and regional parameters of LV remodeling (LVR) as well as contractile reserve and b) the suitability and validity of different echocardiographic methods in this scenario. Murine ventricular cardiomyocytes (E13.5-E16.5) were transplanted into cryolesioned hearts of male HIM-OF1 mice. Echocardiography was performed at rest 4 and 14 days postoperatively. For quantification of akinetic myocardial mass and contractile reserve 2 weeks postoperatively additionally low-dose dobutamine stress echocardiography was conducted. Reconstructive 3D-echocardiography (r3D-echo) was compared to "plain" echocardiographic investigations and was compared to invasive measurements with conduction catheter. CMP significantly attenuated LV dilatation and reduced LV function decline on day 14, as obtained with all echocardiographic modalities and confirmed with conduction catheter measurements. In contrast to plain echocardiography and invasive testing, r3D-echo allowed noninvasive quantification of scar size and assessment of regional contractile reserve. Cell transplanted hearts demonstrated a significant decrease of akinetic myocardial mass (-CMP: 13 ± 2%; +CMP 7 ± 1%; p < 0.001) and increased regional contractile reserve, an indirect sign of myocardial viability. The present study demonstrates beneficial effects of CMP on global and regional parameters of LVR and contractile reserve after MI. In contrast to "simple" 2D echocardiography, r3D-echo allowed the assessment of regional contractile reserve and quantification of akinetic myocardial mass as additive functional and morphological measures of LVR.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Cellular cardiomyoplasty (CMP); Echocardiography; Left ventricular remodeling (LVR); Myocaridal injury

Cardioprotective effects of osteopontin-1 during development of murine ischemic cardiomyopathy - Duerr, Georg D.; Mesenholl, Bettina; Heinemann, Jan C.; Zoerlein, Martin; Huebener, Peter; Schneider, Prisca; Feisst, Andreas; Ghanem, Alexander; Tiemann, Klaus; Dewald, Daniela; Welz, Armin; Dewald, Oliver (BioMed Research International, 2014)
Repetitive brief ischemia and reperfusion (I/R) is associated with ventricular dysfunction in pathogenesis of murine ischemic cardiomyopathy and human hibernating myocardium. We investigated the role of matricellular protein osteopontin-1 (OPN) in murine model of repetitive I/R. One 15-min LAD-occlusion followed by reperfusion was performed daily over 3, 5, and 7 consecutive days in C57/Bl6 wildtype- (WT-) and OPN-/--mice (n = 8 /group). After echocardiography hearts were processed for histological and mRNA-studies. Cardiac fibroblasts were isolated, cultured, and stimulated with TGF-β1. WT-mice showed an early, strong, and cardiomyocyte-specific osteopontin- expression leading to interstitial macrophage infiltration and consecutive fibrosis after 7 days I/R in absence of myocardial infarction. In contrast, OPN-/--mice showed small, nontransmural infarctions after 3 days I/R associated with significantly worse ventricular dysfunction. OPN -/--mice had different expression of myocardial contractile elements and antioxidative mediators and a lower expression of chemokines during I/R. OPN-/--mice showed predominant collagen deposition in macrophage-rich small infarctions. We found lower induction of tenascin-C, MMP-9, MMP-12, and TIMP-1, whereas MMP-13-expression was higher in OPN-/--mice. Cultured OPN-/--myofibroblasts confirmed these findings. In conclusion, osteopontin seems to modulate expression of contractile elements, antioxidative mediators, and inflammatory response and subsequently remodel in order to protect cardiomyocytes in murine ischemic cardiomyopathy. © 2014 Georg D. Duerr et al.
CRIS-Team Scopus Importer:2022-05-03

CB2-deficiency is associated with a stronger hypertrophy and remodeling of the right ventricle in a murine model of left pulmonary artery occlusion - Duerr, Georg Daniel; Feisst, Andreas; Halbach, Katharina; Verfuerth, Luise; Gestrich, Christopher; Wenzel, Daniela; Zimmer, Andreas; Breuer, Johannes; Dewald, Oliver (Life Sciences, 2018)
Aims: Pulmonary hypertension (PH) leads to right ventricular (RV) adaptation and remodeling and has deleterious long-term effects on RV function. The endocannabinoid receptor CB2 has been associated with protective effects in adaptation and remodeling of the left ventricle after ischemia. Therefore, we investigated the role of CB2 receptor in RV adaptation after occlusion of the left pulmonary artery (LPA) in a murine model. Main methods: C57/Bl6 (WT)- and CB2 receptor-deficient (Cnr2−/−)-mice underwent paramedian sternotomy and LPA was occluded using a metal clip. Right heart hemodynamic study (Millar®) preceded organ harvesting for immunohistochemistry and mRNA analysis 7 and 21 days (d) post-occlusion. Key findings: LPA occlusion led to higher RV systolic pressure in Cnr2−/−-hearts, while hemodynamics were comparable with WT-hearts after 21d. Cnr2−/−-hearts showed higher macrophage infiltration and lower interleukin-10 expression after 7 d, but otherwise a comparable inflammatory mediator expression profile. Cardiomyocyte-hypertrophy was stronger in Cnr2−/−-mice, presenting with higher tenascin-C expression than WT-hearts. Planimetry revealed higher collagen area in Cnr2−/−-hearts and small areas of cardiomyocyte-loss. Surrounding cardiomyocytes were cleaved caspase-3- and TUNEL positive in Cnr2−/−-hearts. This was associated by maladaptation of myosin heavy-chain isoforms and lower reactive oxygen scavenger enzymes induction in Cnr2−/−-hearts. We found comparable morphological changes in both lungs between the two genotypes. Significance: LPA occlusion led to increased systolic pressure and adaptation of RV in CB2-deficient mice. CB2 receptor seems to modulate RV adaptation through expression of contractile elements, reactive oxygen scavenger enzymes, and inflammatory response in order to prevent cardiomyocyte apoptosis.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Cardiac remodeling; Endocannabinoids; Pulmonary hypertension

CB2 receptor-mediated effects of pro-inflammatory macrophages influence survival of cardiomyocytes - Heinemann, Jan C.; Duerr, Georg D.; Keppel, Katharina; Breitbach, Martin; Fleischmann, Bernd K.; Zimmer, Andreas; Wehner, Sven; Welz, Armin; Dewald, Oliver (Life Sciences, 2015)
Aims The endocannabinoid system and cannabinoid receptor 2 (CB2 receptor) have been associated with modulation of inflammatory response and myocardial adaptation after ischemic injury. In order to elucidate CB2 receptor-related effects during cellular interactions, we investigated cardiomyocyte survival and macrophage function in vitro. Main methods Murine embryonic (eCM) and adult (CM) cardiomyocytes, murine macrophages (MO), and their subtypes M1 (M1-MO) and M2 (M2-MO) were derived from wildtype- (WT) and CB2 receptor-deficient (Cnr2-/-) mice. Cells were cultured separately or in co-culture under normoxia or hypoxia (2% O2) and pro-inflammatory stimulation using interferon (IFN)γ. Besides immunohistochemistry, we also measured mRNA expression (Taqman®) and performed FACS-analysis of cardiomyocytes. Macrophage migration was assessed using Boyden chamber assay. Key findings We found a significant induction of CB2 receptor mRNA and protein in murine eCM as well as M1- and M2-MO in vitro following cultivation under hypoxia or stimulation with IFNγ. A significantly higher amount of apoptotic Cnr2-/--CMs was found after incubation under hypoxia when compared to WT-CMs. We observed a significantly stronger migration potential in Cnr2-/--M1-MOs towards the supernatant of apoptotic CM, than in corresponding WT-cells. Co-culture revealed a significantly higher loss of eCMs and induction of their apoptosis after cultivation with Cnr2-/--M1-MOs. Production of TNF-α in M1-MOs was dependent on CB2 receptor stimulation by anandamide. Significance Our data provide novel insights into CB2 receptor-mediated protection of cardiomyocytes during hypoxia and pro-inflammatory stimulation. We show CB2 receptor-dependent effects on migration and function of M1-MOs in interaction with cardiomyocytes, thereby influencing their survival.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Cardiomyocytes; CB2 receptor; Endocannabinoids; Inflammation; Macrophages

Changes of the nociceptive flexion reflex threshold in patients undergoing cardiac surgery-a prospective clinical pilot study - Borngaesser, Felix; Bantel, Carsten; Dewald, Oliver; Book, Malte; Weyland, Andreas; Guenther, Ulf (Journal of Clinical Monitoring and Computing, 2022)
Opioid dosage for general anaesthesia and sedation relies on surrogate parameters such as heartrate and blood pressure. This implies the risk of both under- and overdosing. A promising tool to provide target-oriented opioid dosing is measuring the nociceptive flexion reflex threshold (NFRT). The aim of this study was to investigate the individual trajectories and to determine this methods' clinical practicability in the perioperative setting of cardiac surgery. NFRT was measured preoperatively (twice as baseline), immediately after surgery and later in the general ward (primary outcomes). No intraoperative measurements were performed since neuromuscular blockade hinders NFRT assessment. Administered analgesics and pain scores were also recorded (secondary outcomes). Data were collected from August 2019 to March 2020. 264 patients scheduled for cardiac surgery were screened for eligibility. 55 patients were included, 30 rendered datasets for analysis. Thresholds after conclusion of surgery [T-ICU: median (IQR), 31.1 mA (21.5-50.0 mA)] were significantly higher than preoperatively [T-pre: 9.2 mA (5.4-13.4 mA); P < 0.001]. In 11 patients (36.7%), no immediate postoperative reflex response was elicited. Later, all reflexes returned, but thresholds remained significantly higher than preoperatively [T-post: 11.9 mA (9.2-16.6 mA); P = 0.043]. NFRT values after surgery were higher compared to baseline measurements. Subsequently they decreased but did not reach their baseline levels. There was no corresponding dose-dependency, suggesting multimodal effects on the nociceptive system. Unless measurements are not prevented by technical issues NFRT-assessment appears to be a future tool to target analgesics in patients not able to self-report pain.
CRIS-Team WoS Importer:2023-01-13

Comparison of myocardial remodeling between cryoinfarction and reperfused infarction in mice - Duerr, Georg D.; Elhafi, Naziha; Bostani, Toktam; Ellinger, Jörg; Swieny, Louay; Kolobara, Elvis; Welz, Armin; Dewald, Oliver (Journal of Biomedicine and Biotechnology, 2011)
Myocardial infarction is associated with inflammatory reaction leading to tissue remodeling. We compared tissue remodeling between cryoinfarction (cMI) and reperfused myocardial infarction (MI) in order to better understand the local environment where we apply cell therapies. Models of closed-chest one-hour ischemia/reperfusion MI and cMI were used in C57/Bl6-mice. The reperfused MI showed rapid development of granulation tissue and compacted scar formation after 7 days. In contrast, cMI hearts showed persistent cardiomyocyte debris and cellular infiltration after 7 days and partially compacted scar formation accompanied by persistent macrophages and myofibroblasts after 14 days. The mRNA of proinflammatory mediators was transiently induced in MI and persistently upregulated in cMI. Tenascin C and osteopontin-1 showed delayed induction in cMI. In conclusion, the cryoinfarction was associated with prolonged inflammation and active myocardial remodeling when compared to the reperfused MI. These substantial differences in remodeling may influence cellular engraftment and should be considered in cell therapy studies. Copyright © 2011 Georg D. Duerr et al.
CRIS-Team Scopus Importer:2022-05-03

Comparison of stroke volumes assessed by three-dimensional echocardiography and transpulmonary thermodilution in a pediatric animal model - Linden, Katharina; Ladage, Dennis; Dewald, Oliver; Gatzweiler, Eva; Pieper, Andrea; Seehase, Matthias; Duerr, Georg Daniel; Breuer, Johannes; Herberg, Ulrike (Journal of Clinical Monitoring and Computing, 2017)
To compare stroke volumes (SV) in small hearts assessed by real-time three-dimensional echocardiography (3DE) with SV measured by transpulmonary thermodilution (TPTD) and continuous pulse contour analysis (PC) under various hemodynamic conditions. In thirteen anesthetized piglets (range 3.6–7.1 kg) SV were measured by 3DE, TPTD and PC at baseline and during phenylephrine and esmolol administration. 3DE and TPTD measurements were done successively while SV calculated by PC was documented at the time of 3DE. 3DE and TPTD showed a good correlation (r2 = 0.74) and a bias of −1.3 ml (limits of agreement −4.1 to 1.5 ml). While TPTD measured higher SV than 3DE, both methods tracked SV changes with a concordance rate of 91 %. PC and 3DE showed a lower correlation coefficient of r2 = 0.57 and a bias of −2.1 ml (limits of agreement −5.9 to 1.8 ml). Inter- and intra-observer variability of SV measured by 3DE was good with a mean bias <5 %. SV3DE showed a small variance and tracked acute small changes in SV in acceptable concordance with TPTD. PC measured SV with a higher variance and mean difference compared to 3DE. In an experimental setting 3DE has the possibility to offer non-invasive assessments of ventricular volumes volume changes. To determine whether 3DE could be used for SV assessment in a clinical routine our results need confirmation in a clinical setting.
CRIS-Team Scopus Importer:2022-05-03
Keywords: 3-Dimensional echocardiography; Hemodynamics; Pulse contour analysis; Small hearts; Stroke volume; Transpulmonary thermodilution

Continuous Long-Term Assessment of Heart Rate Variability in Adults with Cyanotic Congenital Heart Disease after Surgical Repair - Pieringer, Felix; Suleiman, Mathieu; Kaemmerer-Suleiman, Ann-Sophie; Dewald, Oliver; Freiberger, Annika; Huntgeburth, Michael; Nagdyman, Nicole; Neidenbach, Rhoia; von Scheidt, Fabian; Kaemmerer, Harald; Ewert, Peter; Weyand, Michael; et al. (Journal of Clinical Medicine, 2024)
Background: Heart rate variability (HRV) is an established, non-invasive parameter for the assessment of cardiac autonomic nervous activity and the health status in general cardiology. However, there are few studies on HRV in adults with congenital heart defects (CHDs). The aim of the present study was to evaluate the use of long-term continuous HRV measurement for the assessment of global health status in adults with cyanotic CHD. Methods: This prospective study included 45 adults (40% female, mean age = 35.2 ± 9.2 [range: 19–58] years) after cardiac surgical repair. HRV parameters were calculated from continuous 24 h measurements using a Bittium Faros 180 sensor (Bittium Corp., Oulu, Finland). Results: Postoperative patients with transposition of the great arteries (TGA) (n = 18) achieved significantly higher values of standard deviation of NN intervals (SDNN) (175.4 ± 59.9 ms vs. 133.5 ± 40.6 ms; p = 0.013) compared with patients with other conotruncal anomalies (n = 22). Comparing patients with TGA after a Senning–Brom or Mustard operation (n = 13) with all other heart surgery patients (n = 32), significantly higher HRV parameters were found after atrial switch (root mean square of successive RR interval differences: 53.6 ± 20.7 ms vs. 38.4 ± 18.3 ms; p = 0.019; SDNN: 183.5 ± 58.4 ms vs. 136.3 ± 45.3 ms; p = 0.006). A higher SDNN was also measured after Senning–Brom or Mustard operations than after a Rastelli operations (n = 2) (SDNN: 183.5 ± 58.4 ms vs. 84.5 ± 5.2 ms; p = 0.037). When comparing atrial switch operations (n = 3) with Rastelli operations, the SDNN value was significantly shorter in the Rastelli group (p = 0.004). Conclusions: Our results suggest that continuous HRV monitoring may serve as a marker of cardiac autonomic dysfunction in adults with cyanotic CHD after surgical repair. Impaired cardiac autonomic nervous activity may be associated with an increased risk of adverse reactions in patients with repaired CHD. Therefore, a longitudinal assessment of HRV patterns and trends may provide a deeper insight into dynamic changes in their autonomic regulation and disease progression, lifestyle changes, or treatments. As each person has individual variability in heart rate, HRV may be useful in assessing intra-individual disease progression and may help to improve personalized medicine. Further studies are needed to better understand the underlying mechanisms and to explore the full potential of HRV analysis to optimize medical care for ACHDs.
CRIS-Team Scopus Importer:2024-04-19
Keywords: ACHD; adults with congenital heart disease; arterial switch; atrial switch; cardiac surgery; complete transposition of the great arteries; cyanotic congenital heart defects; heart rate variability; Rastelli operation

CpG postconditioning after reperfused myocardial infarction is associated with modulated inflammation, less apoptosis, and better left ventricular function - Duerr, Georg Daniel; Wu, Shuijing; Schneider, Max Lukas; Marggraf, Vanessa; Weisheit, Christina Katharina; Velten, Markus; Verfuerth, Luise; Frede, Stilla; Boehm, Olaf; Treede, Hendrik; Dewald, Oliver; Baumgarten, Georg; et al. (American Journal of Physiology-Heart and Circulatory Physiology, 2020)
Postconditioning attenuates inflammation and fibrosis in myocardial infarction (MI). The aim of this study was to investigate whether postconditioning with the cytosine-phosphate-guanine (CpG)-containing Toll-like receptor-9 (TLR9) ligand 1668-thioate (CpG) can modulate inflammation and remodeling in reperfused murine MI. Thirty minutes of left descending coronary artery (LAD) occlusion was conducted in 12-wk-old C57BL/6 mice. Mice were treated with CpG intraperitoneally 5 min before reperfusion. The control group received PBS; the sham group did not undergo ischemia. M-mode echocardiography (3, 7, and 28 days) and Millar left ventricular (LV) catheterization were performed (7 and 28 days) before the hearts were excised and harvested for immunohistochemical (6 h, 24 h, 3 days, 7 days, and 28 days), gene expression (6 h, 24 h, and 3 days; Taqman RT-qPCR), protein, and FACS analysis (24 h and 3 days). Mice treated with CpG showed significantly better LV function after 7 and 28 days of reperfusion. Protein and mRNA expressions of proinflammatory and anti-inflammatory cytokines were significantly induced after CpG treatment. Histology revealed fewer macrophages in CpG mice after 24 h, confirmed by FACS analysis with a decrease in both classically M1- and alternative M2a-monocytes. CpG treatment reduced apoptosis and cardiomyocyte loss and was associated with induction of adaptive mechanisms, e.g., of heme-oxigenase-1 and β-/α-myosin heavy chain (MHC) ratio. Profibrotic markers collagen type Iα (Col-Iα) and Col-III induction was abrogated in CpG mice, accompanied by fewer myofibroblasts. This led to the formation of a smaller scar. Differential matrix metalloproteinase (MMP)/tissue inhibitor of metalloproteinase (TIMP) expression contributed to attenuated remodeling in CpG, resulting in preserved cardiac function in a Toll-like receptor 1- and TLR9-dependent manner. Our study suggests a cardioprotective mechanism of CpG postconditioning, involving Toll-like receptor-driven modulation of inflammation. This is followed by attenuated remodeling and preserved LV function. NEW & NOTEWORTHY Cytosine-phosphate-guanine (CpG) postconditioning seems to mediate inflammation via Toll-like receptor-1 and Toll-like receptor-9 signaling. Enhanced cytokine and chemokine expressions are partly attenuated by IL-10 and matrix metalloproteinase-8 (MMP8) induction, being associated with lower macrophage infiltration and M1-monocyte differentiation. Furthermore, switch from α- to β-MHC and balanced MMP/TIMP expression led to lesser cardiomyocyte apoptosis, smaller scar size, and preserved cardiac function. Data of pharmacological postconditioning have been widely disappointing to date. Our study suggests a new pathway promoting myocardial postconditioning via Toll-like receptor activation.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Inflammation; Myocardial infarction; Postconditioning; Remodeling; Toll-like receptors

DHA Supplementation Attenuates MI-Induced LV Matrix Remodeling and Dysfunction in Mice - Habicht,; Mohsen, G.; Eichhorn, Lars; Frede, S.; Weisheit, C.; Hilbert, T.; Treede, H.; Gresir, E.; Duerr, G. D.; Velten, Markus; Dewald, Oliver (Oxidative Medicine and Cellular Longevity, 2020)
Objective. Myocardial ischemia and reperfusion (I/R) injury is associated with oxidative stress and inflammation, leading to scar development and malfunction. The marine omega-3 fatty acids (ω-3 FA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA) are mediating cardioprotection and improving clinical outcomes in patients with heart disease. Therefore, we tested the hypothesis that docosahexaenoic acid (DHA) supplementation prior to LAD occlusion-induced myocardial injury (MI) confers cardioprotection in mice. Methods. C57BL/6N mice were placed on DHA or control diets (CD) beginning 7 d prior to 60 min LAD occlusion-induced MI or sham surgery. The expression of inflammatory mediators was measured via RT-qPCR. Besides FACS analysis for macrophage quantification and subtype evaluation, macrophage accumulation as well as collagen deposition was quantified in histological sections. Cardiac function was assessed using a pressure-volume catheter for up to 14 d. Results. DHA supplementation significantly attenuated the induction of peroxisome proliferator-activated receptor-α (PPAR-α) (2.3±0.4 CD vs. 1.4±0.3 DHA) after LAD occlusion. Furthermore, TNF-α (4.0±0.6 CD vs. 1.5±0.2 DHA), IL-1β (60.7±7.0 CD vs. 11.6±1.9 DHA), and IL-10 (223.8±62.1 CD vs. 135.5±38.5 DHA) mRNA expression increase was diminished in DHA-supplemented mice after 72 h reperfusion. These changes were accompanied by a less prominent switch in α/β myosin heavy chain isoforms. Chemokine mRNA expression was stronger initiated (CCL2 6 h: 32.8±11.5 CD vs. 78.8±13.6 DHA) but terminated earlier (CCL2 72 h: 39.5±7.8 CD vs. 8.2±1.9 DHA; CCL3 72 h: 794.3±270.9 CD vs. 258.2±57.8 DHA) in DHA supplementation compared to CD mice after LAD occlusion. Correspondingly, DHA supplementation was associated with a stronger increase of predominantly alternatively activated Ly6C-positive macrophage phenotype, being associated with less collagen deposition and better LV function (EF 14 d: 17.6±2.6 CD vs. 31.4±1.5 DHA). Conclusion. Our data indicate that DHA supplementation mediates cardioprotection from MI via modulation of the inflammatory response with timely and attenuated remodeling. DHA seems to attenuate MI-induced cardiomyocyte injury partly by transient PPAR-α downregulation, diminishing the need for antioxidant mechanisms including mitochondrial function, or α-to β-MHC isoform switch.
CRIS-Team Scopus Importer:2022-05-03

Disorientation and delirium assessment: A secondary analysis of a prospective, observational study Bedeutung der Desorientierung bei der Delireinschätzung: Sekundäranalyse einer prospektiven, observationellen Studie - Guenther, Ulf; Wolke, Mirko; Hansen, Hans-Christian; Feldmann, Nicole; Diers, Anja; Dewald, Oliver; Ely, E. Wesley; Weyland, Andreas (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2021)
Disorientation may present as a warning sign of developing delirium. The most commonly used delirium assessment tool in Germany, the Confusion Assessment Method for Intensive Care Unit (CAM-ICU), does not rate “disorientation”, since intubated patients cannot communicate verbally. However, the majority of German ICU patients are not orally intubated, so they could be examined for their orientation. This study was carried out to investigate whether the delirium feature “disorientation” in extubated patients yields diverging findings in comparison to the CAM-ICU and whether the sensitivity of the CAM-ICU may be improved when combined with the feature “disorientation” (CAM-IMC). A total of 86 paired assessments were completed in 50 extubated patients. Delirium was found in 19.8% (N = 17). The CAM-ICU had a sensitivity of 71% (95% confidence interval [CI] 44–90%) and a specificity of 100% (95–100%). Disorientation, if taken as the only delirium feature, had a sensitivity of 77% (50–93%) and a specificity of 93% (89–100%). The CAM-IMC reached a sensitivity of 88% (64–99%) and a specificity of 100% (95–100%). The receiver operating characteristics (ROC) analyses found an area under the curve (AUC) of 0.941 (95%CI 0.851–1.000) for the CAM-IMC, which was the highest compared to the other delirium tests (CAM-ICU, AUC 0.853 [0.720–0.986]; disorientation, AUC 0.868 [0.745–0.991]). This research emphasizes the importance of the feature “disorientation” for delirium assessments in patients able to verbally communicate and explains some controversial delirium ratings in daily practice. The CAM-IMC appears to be an attractive tool for delirium assessment in nonintubated patients and deserves further research.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Cardiac surgery; Confusion; Intensive care unit; Intermediate care; Postoperative

Disorientation as a delirium feature in non-intubated patients: development and evaluation of diagnostic accuracy of the ‘Confusion Assessment Method for Intermediate Care Unit’ (CAM-IMC) - a prospective cohort study - Beyer, L. P.; Gathen, L. von zur; Rayah, B. El; Dewald, Oliver; Zieschang, T.; Diers, A.; Ely, E. Wesley; Guenther, U. (BMC Anesthesiology, 2024)
Background: Disorientation is an early indicator of developing postoperative delirium (POD), which is associated with increased mortality and cognitive decline. The well-established “Confusion-Assessment-Method-for-Intensive-Care-Unit” (CAM-ICU) for diagnosing POD in intubated patients cannot make use of the feature ‘disorientation’, as this requires verbal communication. Other tools such as the 4AT test for disorientation but are not established in ICU settings. We therefore combined test-variables of the CAM-ICU (level of consciousness, fluctuating mental status and inattention) with verbal testing for disorientation to develop and enhance diagnostic accuracy of the “Confusion Assessment Method for Intermediate Care Unit” (CAM-IMC). In the present study we describe the development and the evaluation of the diagnostic accuracy of the CAM-IMC. Methods: We conducted a prospective cohort-study to develop and evaluate the diagnostic accuracy of the CAM-IMC and disorientation for diagnosing POD in non-intubated patients undergoing elective cardiac surgery. All patients were eligible during data collection period. Exclusion criteria were preexisting brain-organic disease, age < 50 years, preoperative intubation, and insufficient language skills. Patients were assessed for POD using the CAM-IMC as the index-test by two independent examiners over three postoperative days. Reference-testing was conducted by experienced reference-raters. The primary outcome was the diagnostic test-performance. Results: Among 178 eligible patients, 624 paired observations were completed with 155 patients. Of these, 9% experienced POD. Sensitivity and specificity were 0.96 (CI-95%: 0.87-1.00) and 0.94 (CI-95%: 0.92–0.96), respectively. Area-Under-the-Receiver-Operating-Characteristic-Curve (AUROC; equivalent to c-statistic) for CAM-IMC with a cut-off at three points was 0.95 (CI-95%: 0.93–0.98). The interrater reliability was 0.80 (CI-95%: 0.69–0.91). Conclusion: The CAM-IMC demonstrates excellent test performance for diagnosing POD in non-intubated patients by combining features of the CAM-ICU with ‘disorientation’. Given an aging community with an increasing delirium risk, the CAM-IMC provides a highly structured assessment tool for POD. It enables early and accurate detection of delirium, which is critical for timely intervention and improved patient outcomes. The CAM-IMC appears to be a useful tool to be implemented in units for not-intubated patients and seems to be the perfect match where the CAM-ICU is already in use for monitoring POD. Trial registration: DRKS00026980 (German registry of clinical studies).
CRIS-Team Scopus Importer:2025-02-04
Keywords: CAM-ICU; CAM-IMC; Delirium; Disorientation; Non-intubated; POD

Early postnatal echocardiographic assessment of pulmonary blood flow in newborns with congenital diaphragmatic hernia - Kipfmueller, Florian; Heindel, Katrin; Schroeder, Lukas; Berg, Christoph; Dewald, Oliver; Reutter, Heiko M.; Bartmann, Peter; Mueller, Andreas (Journal of Perinatal Medicine, 2018)
Echocardiography is the most important tool to assess infants with congenital diaphragmatic hernia (CDH) for pulmonary hypertension (PH). The pattern of blood flow in the pulmonary artery [described as time to peak velocity (TPV)/right ventricular ejection time (RVET) ratio] provides distinct information about pulmonary arterial pressure. The aim of our study was to investigate the correlation of TPV/RVET measurements with the most commonly used classification system for PH in CDH newborns and the association of these measurements with outcome parameters. Echocardiographic measurements were obtained in 40 CDH newborns within 6 h of life. The obtained measurements were correlated with the decision for or against extracorporeal membrane oxygenation (ECMO); early mortality; total duration of mechanical ventilation and total duration of oxygen supplementation. The correlation coefficient between severity of PH and TPV/RVET measurements was -0.696 (P<0.001). Using receiver operating characteristic (ROC) analyses the optimal cutoff for TPV/RVET in order to predict the necessity for ECMO or early mortality without ECMO was 0.29 with a sensitivity of 86.7%, a specificity of 68%, a positive predictive value of 61.9% and a negative predictive value of 89.5%. Newborns with a TPV/RVET below the cutoff had a 5.9-fold risk for ECMO or early mortality, a significantly longer duration of mechanical ventilation (13.4 days vs. 7.4 days, P=0.003) and oxygen supplementation (22.4 days vs. 9.0 days, P=0.019), and a lower survival rate (76.2% vs. 100%, P=0.021). TPV/RVET is a feasible parameter to assess PH in CDH newborns with close correlation to outcome parameters.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Acceleration time; congenital diaphragmatic hernia; echocardiography; ECMO; pulmonary hypertension; time to peak velocity

Endocannabinoids in adaptation to injury: Ready to move from bench to bedside? - Dewald, Oliver; Zimmer, Andreas (Life Sciences, 2015)
CRIS-Team Scopus Importer:2022-05-03

Erratum to: Intraoperative transösophageale Echokardiographie in der Herzchirurgie mit Fokus auf die Mitralklappenrekonstruktion (Zeitschrift für Herz-,Thorax- und Gefäßchirurgie, (2024), 38, 1, (37-51), 10.1007/s00398-023-00631-0) - Krajinovic, Ljubica; Fechner, Jörg; Einhaus, Friedrich; Francis, Roland; Nooh, Ehab; Czesla, M.; Dewald, Oliver; Heim, Christian (Zeitschrift für Herz-, Thorax- und Gefäßchirurgie, 2024)
CRIS-Team Scopus Importer:2024-03-29

Extracorporeal membrane oxygenation support in a newborn with lower urinary tract obstruction and pulmonary hypoplasia: A case report - Gatzweiler, Eva; Hoppe, Bernd; Berg, Christoph; Müller, Andreas; Reutter, Heiko Martin; Kipfmueller, Florian; Dewald, Oliver (Journal of Medical Case Reports, 2018)
Background: Survival of neonates with intrauterine renal insufficiency and oligo- or anhydramnios correlates with the severity of secondary pulmonary hypoplasia. Early prenatal diagnosis together with repetitive amnioinfusions and modern intensive care treatment have improved the prognosis of these neonates. Extracorporeal membrane oxygenation is an established treatment option, mainly applied to neonates with pulmonary hypoplasia caused by congenital diaphragmatic hernia. However, a few case reports of extracorporeal membrane oxygenation in neonates with lower urinary tract obstruction have been published. Case presentation: We describe a case of a Caucasian male infant with prenatally diagnosed lower urinary tract obstruction and secondary pulmonary hypoplasia who was delivered spontaneously at 36 + 2 weeks of gestation. Venovenous extracorporeal membrane oxygenation was initiated on the first day of life for severe respiratory failure and consecutive hypoxemia despite treatment with inhaled nitric oxide and high-frequency oscillation. The patient was supported by extracorporeal membrane oxygenation for 10 days and extubated 6 weeks later. Hemofiltration was required on the second day of life because of renal insufficiency and was later replaced by peritoneal dialysis. The child was discharged after 4 months with nasal high-flow mild oxygen therapy and peritoneal dialysis. Conclusion: Neonatal extracorporeal membrane oxygenation support is a possible treatment option for neonates with lower urinary tract obstruction and pulmonary hypoplasia.
CRIS-Team Scopus Importer:2022-05-03
Keywords: ECMO; Hemofiltration; LUTO; Peritoneal dialysis; Pulmonary hypoplasia

Impact of pre-existing comorbidities on outcomes of patients undergoing surgical aortic valve replacement – rationale and design of the international IMPACT registry - Bakhtiary, Farhad; Ahmad, Ali El-Sayed; Autschbach, Ruediger; Benedikt, Peter; Bonaros, Nikolaos; Borger, Michael; Dewald, Oliver; Feyrer, Richard; Geissler, Hans-Joachim; Gruenenfelder, Juerg; Lam, Ka Yan; Leyh, Rainer; et al. (Journal of Cardiothoracic Surgery, 2021)
Background: Degenerative aortic valve disease accounts for 10–20% of all cardiac surgical procedures. The impact of pre-existing comorbidities on the outcome of patients undergoing surgical aortic valve replacement (SAVR) needs further research. Methods: The IMPACT registry is a non-interventional, prospective, open-label, multicenter, international registry with a follow-up of 5 years to assess the impact of pre-existing comorbidities of patients undergoing SAVR with the INSPIRIS RESILIA aortic valve on outcomes. IMPACT will be conducted across 25 sites in Austria, Germany, The Netherlands and Switzerland and intends to enroll approximately 500 patients. Patients will be included if they are at least 18 years of age and are scheduled to undergo SAVR with the INSPIRIS RESILIA Aortic Valve with or without concomitant ascending aortic root replacement and/or coronary bypass surgery. The primary objective is to determine all-cause mortality at 1, 3, and 5 years post SAVR. Secondary objectives include cardiac-related and valve-related mortality and structural valve deterioration including hemodynamics and durability, valve performance and further clinical outcomes in the overall study population and in specific patient subgroups characterized by the presence of chronic kidney disease, hypertension, metabolic syndrome and/or chronic inflammation. Discussion: IMPACT is a prospective, multicenter European registry, which will provide much-needed data on the impact of pre-existing comorbidities on patient outcomes and prosthetic valve performance, and in particular the performance of the INSPIRIS RESILIA, in a real-world setting. The findings of this study may help to support and expand appropriate patient selection for treatment with bioprostheses. Trial registration: ClinicalTrials.gov identifier: NCT04053088.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Aortic valve disease; Comorbidities; Real-world setting; SAVR; Surgical aortic valve replacement

Impaired border zone formation and adverse remodeling after reperfused myocardial infarction in cannabinoid CB2 receptor deficient mice - Duerr, Georg D.; Heinemann, Jan C.; Gestrich, Christopher; Heuft, Tobias; Klaas, Timo; Keppel, Katharina; Roell, Wilhelm; Klein, Alexandra; Zimmer, Andreas; Velten, Markus; Kilic, Ana; Bindila, Laura; et al. (Life Sciences, 2015)
Aims: Reperfusion ofmyocardial infarction is associated with inflammatory reaction and subsequentmyocardial remodeling with a rapid scar formation in mice. The cannabinoid receptor CB2 has been associated with cardioprotection and regulation ofmacrophage function.Weinvestigated its role in remodeling of reperfused infarction. Main methods: One hour LAD-occlusion was followed by reperfusion over 6 h and 1, 3 and 7 days in wild-type C57/BL6J (WT) and CB2 receptor-deficient (Cnr2-)mice (n=8/group). Hearts were processed for functional, morphological and mRNA/protein analysis, and tissue concentration of endocannabinoidswas determined using liquid chromatography-multiple reaction monitoring. Key findings: In contrast to a rapid formation of granulation tissue and a compacted non-transmural scar inWT mice after 7 days of reperfusion, Cnr2-/- mice showed a non-compacted transmural scar. Millar left ventricular catheter measurements revealed a significantly worse function in Cnr2- mice.We found no compensatory elevation of endocannabinoid concentration in Cnr2-/- hearts. Macrophage infiltration was significantly stronger in Cnr2- hearts and affected also the remote septum, when compared to WT hearts.We found a cytokine-driven inflammatory response in Cnr2- hearts with no significant induction of chemokines. Immunohistochemistry for thrombospondin-1 revealed a dysfunctional infarction border zone formation in Cnr2- hearts. Cnr2- hearts showed no significant induction of tenascin C, collagen-Ia or lysil oxidase, thereby indicating adversemyocardial remodeling. Significance: Endocannabinoids act via CB2 receptor in the modulation of inflammatory response and myocardial remodeling after infarction. CB2 receptor plays an important role in the formation of infarction border zone, collagen deposition and organization of stable scar during remodeling.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Endocannabinoids; Infarction border zone; Ischemia; Reperfusion; Thrombospondin

Independent factors for the development of vasoplegic syndrome in patients undergoing coronary artery bypass surgery - Palm, Constantin L.; Baumhove, Lukas; Pabst, Simon; Guenther, Ulf; Book, Malte; Chaduneli, Onise; Martens, Andreas; Mellert, Friedrich; Dewald, Oliver (Frontiers in Cardiovascular Medicine, 2024)
Objective: Vasoplegic syndrome remains a common complication of cardiac surgery. It has serious implications for the healthcare system and individual patients, as it leads to rising healthcare costs and higher mortality. A better understanding of factors triggering vasoplegic syndrome is essential for the development of effective prevention strategies. We aimed to identify clinical characteristics and intraoperative parameters associated with the development of vasoplegic syndrome in coronary artery bypass graft surgery and the influence of vasoplegia on outcome. Methods: We retrospectively analyzed the data of all patients who underwent isolated coronary artery bypass graft surgery or coronary artery bypass graft surgery combined with atrial appendage occlusion, using the heart-lung machine at our institution from 04/2019 to 12/2020. Vasoplegic syndrome was defined as MAP ≤60 mmHg and norepinephrine equivalence dosage of ≥0.2 μg/kg/min with a central venous saturation ≥60% within 2 days from surgery. Results: Of 647 patients included in this study, 72 (11.1%) developed vasoplegic syndrome. Patients experiencing vasoplegia had longer stay in ICU, more frequently underwent tracheostomy and suffered more often from pneumonia. The duration of extracorporeal circulation, intraoperative application of platelet concentrates and usage of cold crystalloid cardioplegia (Bretschneider) independently predicted development of vasoplegic syndrome. Conclusions: Even in relatively low-risk cardiac surgery, vasoplegic syndrome is a common complication and was associated with serious adverse effects. The use of warm blood cardioplegia (Calafiore) seems to be safer than cold crystalloid cardioplegia (Bretschneider) and might be preferable in patients that are vulnerable to the consequences of vasoplegic syndrome.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Bretschneider cardioplegia; coronary artery bypass graft surgery; extracorporeal circulation (ECC); vasoplegic syndrome; warm blood cardioplegia

Intraoperative transösophageale Echokardiographie in der Herzchirurgie mit Fokus auf die Mitralklappenrekonstruktion - Krajinovic, Ljubica; Fechner, Jörg; Einhaus, Friedrich; Francis, Roland; Nooh, Ehab; Czesla, M.; Dewald, Oliver; Heim, Christian (Zeitschrift für Herz-, Thorax- und Gefäßchirurgie, 2024)
Transesophageal echocardiography (TEE) is important for rapid assessment of biventricular function, regional contractility disorders and the integrity of heart valve anatomy and function. Mitral valve regurgitation (MVR) is the second most common valvular heart disease in Europe after aortic valve stenosis. Qualified TEE is indispensable for the success of minimally invasive repair of severe MVR (MIR-MVR). For quantification of MVR the vena contracta area, effective regurgitant orifice area (EROA) determined using the proximal isovelocity surface area (PISA), regurgitant volume and left ventricular endsystolic diameter are utilized for quantification of MVR. Grading of the MVR, the final assessment of the operation results and echocardiographic guidance during critical surgical steps of MIR-MVR are essential. The MIR-MVR is complex and requires an optimal interdisciplinary cooperation.
CRIS-Team Scopus Importer:2024-02-02
Keywords: Diagnostic imaging; Endoaortic occlusion; Heart-lung machine; Minimally invasive surgical procedures; Mitral valve regurgitation

Low-body-perfusion via an arterial sheath reduces inflammation after aortic arch reconstruction surgery - Baehner, Torsten; Breuer, Johannes; Heinze, Ingo; Duerr, Georg Daniel; Velten, Markus; Dewald, Oliver (European Journal of Inflammation, 2021)
Pediatric cardiac surgeries involving aortic arch reconstruction are complex and require long cardiopulmonary bypass (CPB) times with deep hypothermic circulatory arrest (DHCA). Selective perfusion techniques have been developed to prevent the deleterious consequences of DHCA associated hypoperfusion. The effectivity of low body perfusion through cannulation of the femoral artery with an arterial sheath remains to be elucidated. We compared perfusion and inflammation in patients receiving selective antegrade cerebral perfusion (ACP) only to low body perfusion (LBP) in addition to ACP during DHCA for aortic arch reconstruction surgery. There was no difference in patient characteristics, cardiac pathologies, or performed procedures between ACP and LBP groups. Lactate levels increased after cardiac arrest in both groups. However, lactate levels were lower after 1 h reperfusion, at the end of extracorporeal circulation (ECC), and after surgery in LBP group compared to ACP only. Furthermore, creatinine was increased in ACP group on postoperative day 1 compared to LBP group but no acute kidney injury was observed in any group. IL-6 concentration increased in ACP group, while remained unchanged in LBP group compared to pre surgical values and were significantly lower compared to ACP group on postoperative days 1 and 2. LBP via an arterial sheath during cardiac arrest for aortic arch reconstruction surgery in addition to ACP, improves post ECC tissue perfusion as indicated by lower lactate levels and reduces creatinine levels suggesting milder kidney injury. LBP seems to prevent postoperative inflammation through a reduction in procedural duration or enhanced perfusion and thereby improves the outcome after aortic arch reconstruction surgery.
CRIS-Team Scopus Importer:2022-05-03
Keywords: aortic arch reconstruction surgery; low-body-perfusion; pediatric cardiac surgery; selective perfusion

Low cholinesterase activity is a risk factor for delirium after cardiac surgery: A prospective cohort study - Guenther, Ulf; Wolke, Mirko; Schelling, Renke; Kohse, Klaus P.; Book, Malte; Dewald, Oliver; Weyland, Andreas (European Journal of Anaesthesiology, 2021)
CRIS-Team Scopus Importer:2022-05-03

Mechanische Herz-Kreislauf-Unterstützung bei akutem Rechtsherzversagen - Aziz, Saya; Dewald, Oliver; Tandler, Rene; Heim, Christian (Zeitschrift für Herz-, Thorax- und Gefäßchirurgie, 2024)
Right ventricular (RV) failure is associated with significant morbidity and mortality, with in-hospital mortality rates estimated to be as high as 70–75%. The RV failure can occur after cardiac surgery or isolated in certain situations, such as acute myocardial infarction, pulmonary embolism, left ventricular assist device implantation or after heart transplantation. Drug treatment includes fine tuning of the volume status and administration of inotropic agents, vasopressors and pulmonary vasodilators. Selected patients with persistent RV failure may benefit from mechanical circulatory support. Percutaneous and surgical mechanical support systems are increasingly being used. Systems for isolated RV support include percutaneous options, such as micro-axial flow pumps and extracorporeal centrifugal flow support devices as well as surgical options with RV support devices and arteriovenous extracorporeal membrane oxygenation. This review discusses the indications, patient selection, treatment strategies and outcomes of mechanical circulatory support for RV failure.
CRIS-Team Scopus Importer:2024-04-12
Keywords: Acute right heart failure; Arteriovenous extracorporeal membrane oxygenation; Cardiogenic shock; Impella RP; Right ventricular assist devices

Metallothioneins 1 and 2 modulate inflammation and support remodeling in ischemic cardiomyopathy in mice - Duerr, Georg D.; Schmitz, Eva J.; Verfuerth, Luise; Keppel, Katharina; Peigney, Christine; Ghanem, Alexander; Welz, Armin; Dewald, Oliver; et al. (Mediators of Inflammation, 2016)
Aims. Repetitive brief ischemia and reperfusion (I/R) is associated with left ventricular dysfunction during development of ischemic cardiomyopathy. We investigated the role of zinc-donor proteins metallothionein MT1 and MT2 in a closed-chest murine model of I/R. Methods. Daily 15-minute LAD-occlusion was performed for 1, 3, and 7 days in SV129 (WT)- and MT1/2 knockout (M T-/-)-mice (n = 8-10/group). Hearts were examined with M-mode echocardiography and processed for histological and mRNA studies. Results. Expression of MT1/2 mRNA was transiently induced during repetitive I/R in WT-mice, accompanied by a transient inflammation, leading to interstitial fibrosis with left ventricular dysfunction without infarction. In contrast, MT-/- -hearts presented with enhanced apoptosis and small infarctions leading to impaired global and regional pump function. Molecular analysis revealed maladaptation of myosin heavy chain isoforms and antioxidative enzymes in MT1/2-/- -hearts. Despite their postponed chemokine induction we found a higher total neutrophil density and macrophage infiltration in small infarctions in M T-/- -hearts. Subsequently, higher expression of osteopontin 1 and tenascin C was associated with increased myofibroblast density resulting in predominately nonreversible fibrosis and adverse remodeling in MT1/2-/--hearts. Conclusion. Cardioprotective effects of MT1/2 seem to be exerted via modulation of contractile elements, antioxidative enzymes, inflammatory response, and myocardial remodeling.
CRIS-Team Scopus Importer:2022-05-03

Mobility and freedom of movement: A novel out-of-hospital treatment for pediatric patients with terminal cardiac insufficiency and a ventricular assist device - Rottermann, Kathrin; Dittrich, Sven; Dewald, Oliver; Teske, Andreas; Kwapil, Nicola; Bleck, Steffen; Purbojo, Ariawan; Münch, Frank (Frontiers in Cardiovascular Medicine, 2022)
Background: Due to rapid medical and technological progress, more and more pediatric patients with terminal cardiac insufficiency are being implanted with a ventricular assist device as a bridge to transplant without legal approval for hospital discharge. EXCOR (R) Active is a recently developed mobile driving unit for the EXCOR (R) ventricular assist device (EXCOR (R) VAD) with a long-lasting battery life that can manage small blood pumps, offering improved mobility for pediatric patients. This study strives to elaborate the requirements necessary for a safe home healthcare environment (HHE) for pediatric patients on EXCOR (R) VAD powered by the EXCOR (R) Active driving unit. Materials and methods: Patient- and device-related preconditions (medical, ethical, psychological, technical, structural, organizational) were analyzed with regard to feasibility and safety in three individual patient cases. Included were pediatric patients with terminal cardiac insufficiency in a stable medical condition receiving in-hospital treatment with a univentricular or biventricular EXCOR (R) VAD powered by EXCOR (R) Active. Analysis was single-center, data was obtained 05/2020-02/2022. Results: A total of three patients on EXCOR (R) VAD were identified for HHE treatment with the EXCOR (R) Active driving unit. Switch was performed safely and increased mobility led to improved psychomotor development and improved quality of life. No complications directly related to HHE-treatment occurred. One patient recently underwent an orthotopic heart transplant, one patient remains in HHE, and one patient died due to a complication not related to the HHE. Ethical approval for off-label use was obtained and patients and parents were given the required technical training and psychological support. Caregivers and medical professionals involved in the patients' care at home were briefed intensely. Remote consultations were implemented and interdisciplinary in-hospital checks reduced to a long-term 4-week-scheme. Conclusion: While it is challenging to discharge pediatric patients being treated with a paracorporeal ventricular assist device (EXCOR (R) VAD) from hospital, it is feasible and can be managed safely with the novel driving unit EXCOR (R) Active. A HHE may help to improve patients' psychomotor development, offer normalized social contacts and strengthen both patients' and parents' physical and mental resources. Legal approval and another study with a larger sample size are warranted.
CRIS-Team WoS Importer:2022-12-30

Myocardial hypertrophy is associated with inflammation and activation of endocannabinoid system in patients with aortic valve stenosis - Duerr, Georg D.; Heinemann, Jan C.; Dunkel, Silke; Zimmer, Andreas; Lutz, Beat; Lerner, Raissa; Roell, Wilhelm; Mellert, Fritz; Probst, Chris; Esmailzadeh, Bahman; Welz, Armin; Dewald, Oliver (Life Sciences, 2013)
Aims Endocannabinoids and their receptors have been associated with cardiac adaptation to injury, inflammation and fibrosis. Experimental studies suggested a role for inflammatory reaction and active remodeling in myocardial hypertrophy, but they have not been shown in human hypertrophy. We investigated the association of the endocannabinoid system with myocardial hypertrophy in patients with aortic stenosis. Main methods Myocardial biopsies were collected from patients with aortic stenosis (AS) and atrial myxoma as controls during surgery. Histological and molecular analysis of endocannabinoids and their receptors, inflammatory and remodeling-related cells and mediators was performed. Key findings Myocardial hypertrophy was confirmed with significantly higher cardiomyocyte diameter in AS than in myxoma patients, which had normal cell size. AS patients presented compensated myocardial adaptation to pressure overload. AS patients had significantly higher: concentration of endocannabinoid anandamide, expression of its degrading enzyme FAAH, and of cannabinoid receptor CB2, being predominantly located on cardiomyocytes. Cell density of macrophages and newly recruited leukocytes were higher in AS group, which together with increased expression of chemokines CCL2, CCL4 and CXCL8, and suppression of anti-inflammatory IL-10 indicates persistent inflammatory reaction. We found higher myofibroblast density and stronger tenascin C staining along with mRNA induction of tenascin C and CTGF in AS patients showing active myocardial remodeling. Significance Our study shows for the first time activation of the endocannabinoid system and predominant expression of its receptor CB2 on cardiomyocytes being associated with persistent inflammation and active remodeling in hypertrophic myocardium of patients with aortic stenosis. © 2013 Elsevier Inc.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Endocannabinoids; Inflammation; Myocardial hypertrophy; Remodeling

Myocardial maladaptation to pressure overload in CB2 receptor-deficient mice - Duerr, Georg D.; Heinemann, Jan C.; Kley, Julian; Eichhorn, Lars; Frede, Stilla; Weisheit, Christina; Wehner, Sven; Bindila, Laura; Lutz, Beat; Zimmer, Andreas; Dewald, Oliver (Journal of molecular and cellular cardiology, 2019)
Background: Adaptation to aortic valve stenosis leads to myocardial hypertrophy, which has been associated with inflammation, fibrosis and activation of the endocannabinoid system. Since the endocannabinoid system and the CB2 receptor provide cardioprotection and modulate immune response in experimental ischemia, we investigated the role of CB2 in a mouse model of cardiac pressure overload. Methods: Transverse aortic constriction was performed in CB2 receptor-deficient (Cnr2−/−) mice and their wild-type littermates (Cnr2+/+). After echocardiography and Millar left heart catheter hemodynamic evaluation hearts were processed for histological, cellular and molecular analyses. Results: The endocannabinoid system showed significantly higher anandamide production and CB2 receptor expression in Cnr2+/+ mice. Histology showed non-confluent, interstitial fibrosis with rare small areas of cardiomyocyte loss in Cnr2+/+ mice. In contrast, extensive cardiomyocyte loss and confluent scar formation were found in Cnr2−/− mice accompanied by significantly increased apoptosis and left ventricular dysfunction when compared with Cnr2+/+ mice. The underlying cardiac maladaptation in Cnr2−/− mice was associated with significantly reduced expression of myosin heavy chain isoform beta and less production of heme oxygenase-1. Cnr2−/− hearts presented after 7 days with stronger proinflammatory response including significantly higher TNF-alpha expression and macrophage density, but lower density of CD4+ and B220+ cells. At the same time, we found increased apoptosis of macrophages and adaptive immune cells. Higher myofibroblast accumulation and imbalance in MMP/TIMP-regulation indicated adverse remodeling in Cnr2−/− mice. Conclusions: Our study provides mechanistic evidence for the role of the endocannabinoid system in myocardial adaptation to pressure overload in mice. The underlying mechanisms include production of anandamide, adaptation of contractile elements and antioxidative enzymes, and selective modulation of immune cells action and apoptosis in order to prevent the loss of cardiomyocytes.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Adaptive immune cells; Endocannabinoids; Myocardial hypertrophy; Remodeling

Paediatric aortic valve replacement using decellularized allografts: a multicentre update following 143 implantations and five-year mean follow-up - Horke, Alexander; Bobylev, Dmitry; Avsar, Murat; Cvitkovic, Tomislav; Meyns, Bart; Rega, Filip; Hazekamp, Mark; Cesnjevar, Robert; Schmiady, Martin; Staebler, Brigitte; Dewald, Oliver; Ciubotaru, Anatol; et al. (European Journal of Cardio-Thoracic Surgery, 2024)
OBJECTIVES: Decellularized aortic homografts (DAH) were introduced in 2008 as a further option for paediatric aortic valve replacement (AVR). METHODS: Prospective, multicentre follow-up of all paediatric patients receiving DAH for AVR in 8 European centres. RESULTS: A total of 143 DAH were implanted between February 2008 and February 2023 in 137 children (106 male, 74%) with a median age of 10.8years (interquartile range 6.6-14.6). Eighty-four (59%) had undergone previous cardiac operations and 24 (17%) had undergone previous AVR. The median implanted DAH diameter was 21mm (interquartile range 19-23). The median operation duration was 348min (227-439) with a median cardiopulmonary bypass time of 212min (171-257) and a median cross-clamp time of 135min (113- 164). After a median follow-up of 5.3 years (3.3-7.2, max. 15.2 years), the primary efficacy end-points peak gradient (median 14mmHg, 9-28) and regurgitation (median 0.5, interquartile range 0-1, grade 0-3) showed good results but an increase over time. Freedom from death/explantation/endocarditis/bleeding/thromboembolism at 5years were 97.8±1.2/88.7±3.3/99.1±0.9/100 and 99.2±0.8%, respectively. Freedom from death/explantation/endocarditis/bleeding/thromboembolism at 10years were 96.3±1.9/67.1±8.0/93.6±3.9/ 98.6±1.4 and 86.9±11.6%, respectively. In total, 21 DAH were explanted. Seven were replaced by a mechanical AVR, 1 Ross operation was performed and a re-do DAH was implanted in 13 patients with no redo mortality. The calculated expected adverse events were lower for DAH compared to cryopreserved homograft patients (mean age 8.4 years), and in the same range as for Ross patients (9.2 years) and mechanical AVR (13.0 years). CONCLUSIONS: This large-scale prospective analysis demonstrates excellent mid-term survival using DAH with adverse event rates comparable to paediatric Ross procedures.
CRIS-Team Scopus Importer:2024-04-26
Keywords: Allografts; Aortic valve disease; Children; decellularization

PATHFINDER-CHD: prospective registry on adults with congenital heart disease, abnormal ventricular function, and/or heart failure as a foundation for establishing rehabilitative, prehabilitative, preventive, and health-promoting measures: rationale, aims, design and methods - Freilinger, Sebastian; Kaemmerer, Harald; Pittrow, Robert D.; Achenbach, Stephan; Baldus, Stefan; Dewald, Oliver; Ewert, Peter; Freiberger, Annika; Gorenflo, Matthias; Harig, Frank; Hohmann, Christopher; Holdenrieder, Stefan; et al. (Bmc Cardiovascular Disorders, 2024)
Background: Adults with congenital heart defects (ACHD) globally constitute a notably medically underserved patient population. Despite therapeutic advancements, these individuals often confront substantial physical and psychosocial residua or sequelae, requiring specialized, integrative cardiological care throughout their lifespan. Heart failure (HF) is a critical challenge in this population, markedly impacting morbidity and mortality. Aims: The primary aim of this study is to establish a comprehensive, prospective registry to enhance understanding and management of HF in ACHD. Named PATHFINDER-CHD, this registry aims to establish foundational data for treatment strategies as well as the development of rehabilitative, prehabilitative, preventive, and health-promoting interventions, ultimately aiming to mitigate the elevated morbidity and mortality rates associated with congenital heart defects (CHD). Methods: This multicenter survey will be conducted across various German university facilities with expertise in ACHD. Data collection will encompass real-world treatment scenarios and clinical trajectories in ACHD with manifest HF or at risk for its development, including those undergoing medical or interventional cardiac therapies, cardiac surgery, inclusive of pacemaker or ICD implantation, resynchronization therapy, assist devices, and those on solid organ transplantation. Design: The study adopts an observational, exploratory design, prospectively gathering data from participating centers, with a focus on patient management and outcomes. The study is non-confirmatory, aiming to accumulate a broad spectrum of data to inform future hypotheses and studies. Processes: Regular follow-ups will be conducted, systematically collecting data during routine clinical visits or hospital admissions, encompassing alterations in therapy or CHD-related complications, with visit schedules tailored to individual clinical needs. Assessments: Baseline assessments and regular follow-ups will entail comprehensive assessments of medical history, ongoing treatments, and outcomes, with a focus on HF symptoms, cardiac function, and overall health status. Discussion of the design: The design of the PATHFINDER-CHD Registry is tailored to capture a wide range of data, prioritizing real-world HF management in ACHD. Its prospective nature facilitates longitudinal data acquisition, pivotal for comprehending for disease progression and treatment impacts. Conclusion: The PATHFINDER-CHD Registry is poised to offer valuable insights into HF management in ACHD, bridging current knowledge gaps, enhancing patient care, and shaping future research endeavors in this domain.
CRIS-Team Scopus Importer:2024-04-05
Keywords: ACHD; Adult congenital heart disease; Congenital heart defects; Heart failure; Patient outcomes; Prospective registry

Potential Impact of Direct Versus Indirect Central Venoarterial Extracorporeal Membrane Oxygenation (VA-ECMO) Cannulation in Refractory Postcardiotomy Cardiogenic Shock. - Al Ghareeb, Wael; Aldabbas, Mohammad; Ali, Abdou Sheikh; Al-Kassou, Baravan; Gestrich, Christopher; Nickenig, Georg; Dewald, Oliver; Mellert, Fritz (Cureus, 2024)
Background Central venoarterial extracorporeal membrane oxygenation (VA-ECMO) is a commonly employed strategy to support patients in refractory postcardiotomy cardiogenic shock (RPCS). This support can be provided using either indirect central ECMO (icECMO) with a closed thorax or direct central ECMO (dcECMO) with an open thorax. Methods This single-center retrospective analysis included 60 patients undergoing central VA-ECMO for RPCS from January 2019 to December 2020. The primary endpoint of this study is to compare 30-day survival outcomes between the icECMO and dcECMO approaches in RPCS patients. Secondary endpoints include the evaluation of adverse events and the identification of predictors that influence 30-day mortality. Results The study included 60 patients, 25 received icECMO and 35 treated with dcECMO due to RPCS. The icECMO group demonstrated significantly better 30-day survival rates (icECMO; 10 [40%] vs. dcECMO; 5 [14.3%], log-rank test; p=0.042). Despite comparable ECMO flow rate and ECMO RPM (rotations per minute) in the first day between the study groups ([icECMO; 4.5 l/min vs. dcECMO; 4.6 l/min, p=0.124], [icECMO; 3510 rpm vs. dcECMO; 3800 rpm, p=0.115], respectively), lactate levels were significantly higher in the dcECMO group on the 1st and 3rd post-extracorporeal life support (ECLS) days (p=0.006 and p=0.008, respectively). Gastrointestinal ischemia was more common in the dcECMO group (p=0.036). Successful ECMO weaning was more frequent in the icECMO group (56% vs. 22.9%, p=0.014). Multivariable logistic regression identified arterial lactate on the first day with a cutoff 4 mmol/l as an independent risk factor for 30-day mortality with Exp(B) of 8.9 (p=0.007). Conclusions Our findings suggest a potential survival advantage with the icECMO technique in patients undergoing central ECMO cannulation after RPCS. However, larger prospective studies are essential to confirm this observation.
EVALuna2:596901

Preoperative cognitive impairment and postoperative delirium predict decline in activities of daily living after cardiac surgery—a prospective, observational cohort study - Guenther, Ulf; Hoffmann, Falk; Dewald, Oliver; Malek, Ramy; Brimmers, Kathrin; Theuerkauf, Nils; Putensen, Christian; Popp, Julius (Geriatrics, 2020)
Cardiac surgery and subsequent treatment in the intensive care unit (ICU) has been shown to be associated with functional decline, especially in elderly patients. Due to the different assessment tools and assessment periods, it remains yet unclear what parameters determine unfavorable outcomes. This study sought to identify risk factors during the entire perioperative period and focused on the decline in activity of daily living (ADL) half a year after cardiac surgery. Follow-ups of 125 patients were available. It was found that in the majority of patients (60%), the mean ADL declined by 4.9 points (95% CI, −6.4 to −3.5; p < 0.000). In the “No decline”-group, the ADL rose by 3.3 points (2.0 to 4.6; p < 0.001). A multiple regression analysis revealed that preoperative cognitive impairment (MMSE ≤ 26; Exp(B) 2.862 (95%CI, 1.192–6.872); p = 0.019) and duration of postoperative delirium ≥ 2 days (Exp(B) 3.534 (1.094–11.411); p = 0.035) was independently associated with ADL decline half a year after the operation and ICU. Of note, preoperative ADL per se was neither associated with baseline cognitive function nor a risk factor for functional decline. We conclude that the preoperative assessment of cognitive function, rather than functional assessments, should be part of risk stratification when planning complex cardiosurgical procedures.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Activity of daily living; Cardiac; Cognition; Cognitive; Delirium; Intensive care; Older people; Outcomes; Surgery

Priming with synthetic oligonucleotides attenuates pressure overload-induced inflammation and cardiac hypertrophy in mice - Velten, Markus; Duerr, Georg D.; Pessies, Thilo; Schild, Julia; Lohner, Ralph; Mersmann, Jan; Zacharowski, Kai; Klaschik, Sven; Hilbert, Tobias; Hoeft, Andreas; Baumgarten, Georg; Meyer, Rainer; et al. (Cardiovascular Research, 2012)
AimsInflammation and Toll-like receptor (TLR) signalling have been linked to the development of cardiac hypertrophy following transverse aortic constriction (TAC). In the present study, we investigated whether pre-treatment with the synthetic TLR9 ligands 1668-thioate or 1612-thioate modulates the progression of TAC-induced cardiac inflammation and hypertrophy.Methods and resultsC57BL/6N-mice were pre-treated with 1668-thioate, 1612-thioate (0.25 nmol/g, i.p.), or phosphate-buffered saline 16 h prior to TAC or sham surgery. Heart-weight/body-weight ratio (HW/BW), cardiomyocyte cell size, cellular macrophage accumulation, myofibroblast differentiation, and collagen deposition were investigated for up to 28 days. Cardiac function was monitored using a pressure-volume catheter and M-mode echocardiography. Inflammatory gene expression in the heart was analysed via gene array, while the time course of mRNA expression of key inflammatory mediators was assessed via RT-qPCR. TAC increased the HW/BW ratio and cardiomyocyte cell size and induced macrophage accumulation, myofibroblast differentiation, and collagen deposition. These changes were accompanied by cardiac inflammation and a significant loss of left ventricular function. Pre-treatment with cytosine-phosphate-guanine (CpG)-containing 1668-thioate attenuated the inflammatory response, the progression of cardiac hypertrophy, and cardiac remodelling, which resulted in a prolonged preservation of left ventricular function. These changes were induced to a smaller extent by the use of the non-CG-containing oligodeoxynucleotide 1612-thioate.ConclusionPre-treatment with 1668-thioate attenuated cardiac hypertrophy following pressure overload, possibly by modifying the hypertrophy-induced inflammatory response, thereby reducing cardiac growth and fibrosis as well as delaying loss of cardiac function. © 2012 The Author.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Cardiac hypertrophy; Cytokine; Cytosine-phosphate-guanine oligodeoxynucleotide; Inflammation; Innate immunity; Transverse aortic constriction

Psychological burden and coping in destination therapy patients with a left ventricular assist device: A qualitative content analysis - Levelink, Michael; Reinhold, Anna Katharina; Brutt, Anna Levke; Dewald, Oliver (Artificial Organs, 2021)
Background: Due to an increasing prevalence of heart failure and persistent shortage of donor hearts, the number of left ventricular assist device (LVAD) implantations is growing. As more patients live with LVADs for prolonged periods of time, psychosocial outcomes are becoming more relevant. This particularly applies to destination therapy (DT) patients, who live with the LVAD for the rest of their lives. Methods: We used a cross-sectional qualitative design to explore psychological burden, coping strategies, and resources from the perspective of DT patients. Data were collected via semi-structured in-depth interviews with 18 patients who lived with the LVAD for 3 months to over 10 years. These were analyzed using an inductive content analysis. Due to the COVID-19 pandemic, changes to the recruitment strategy and data collection strategies of the original study protocol were applied. Patients and clinicians were involved throughout the research process to ensure the validity of the results and implications. Results: We synthesized 10 psychosocial, health, and treatment-related burdens and identified 15 problem- and emotion-focused coping strategies and 5 personal and environmental resources patients used to cope with the burden. Conclusions: The findings provide deeper insights into the complex and specific situation of LVAD patients to better address the patient situation in health care and promote positive psychosocial outcomes. So far, health care practice and quality vary significantly between clinics due to individual treatment protocols. Our results highlight the need to improve medical and psychosocial care. Overarching care concepts may be developed based on the implications.
CRIS-Team Scopus Importer:2022-05-03

Quality of life after replacement of the ascending aorta in patients with true aneurysms - Lohse, Folke; Lang, Nora; Schiller, Wolfgang; Roell, Wilhelm; Preusse, Claus Juergen; Welz, Armin; Schmitz, Christoph; Dewald, Oliver (Texas Heart Institute Journal, 2009)
True aneurysms of the ascending aorta often remain undetected, yet their sequelae carry a high rate of mortality and morbidity. The operative risk of nonemergent replacement of the ascending aorta is low. It is important to consider quality of life in determining the most appropriate treatment for patients who have aneurysms but have not yet experienced major complications. From January 1999 to December 2003, 134 consecutive patients underwent replacement of a dilated ascending aorta at our center. Another 124 patients with acute or chronic aortic dissections, aortic rupture, or intramural hematoma were excluded. Standard SF-36 and general health questionnaires were sent to all 124 survivors who could be traced. Follow-up was 98.4% complete. The mean age of the survivors was 61.7 ± 11 years, and 63.4% were men. Operative procedures consisted of supracoronary replacement of the ascending aorta in 35.9%, the Wheat procedure in 44%, the David procedure in 11.2%, the Bentall-DeBono procedure in 9%, and the Cabrol procedure in 2.2%. Patients were monitored until May 2005. Thirty-day and midterm mortality rates were 3.7% and 3.9%, respectively. Morbidity due to stroke was 6%, to bleeding 6%, and to myocardial infarction 4.4%. Postoperative qualityof-life evaluation revealed many subscales of SF-36 that were below the norm when compared with a standard population in physically dominated categories. Replacement of the dilated ascending aorta carries acceptable risk in regard to operative death and postoperative quality of life, although this last showed some decline in comparison with quality of life in a normal, healthy population. © 2009 by the Texas Heart® Institute.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Aortic aneurysm; thoracic/surgery; Blood vessel prosthesis; Cardiac surgical procedures/adverse effects; Follow-up studies; Health status indicators; Health surveys; Quality of life; Reference values; Treatment outcome

Rho kinase-1 mediates cardiac fibrosis by regulating fibroblast precursor cell differentiation - Haudek, Sandra B.; Gupta, Damon; Dewald, Oliver; Schwartz, Robert J.; Wei, Lei; Trial, Joann; Entman, Mark L. (Cardiovascular Research, 2009)
AimsHighly proliferative, CD34+/CD45+ fibroblasts derived from monocytic, blood-borne precursor cells play a critical role in the development of fibrosis in a murine ischaemic/reperfusion cardiomyopathy (I/RC) model. The differentiation of human monocytes into fibroblasts in vitro occurs after transendothelial migration (TEM) induced by monocyte chemoattractant protein 1 (MCP-1). Because Rho-associated kinase-1 (ROCK-1) has been implicated in fibrosis and leukocyte TEM, we investigated its involvement in I/RC.Methods and resultsWe subjected mice with genetic deletion of ROCK-1 to I/RC. We found that ROCK-1-/- mice did not develop the fibrosis and cardiac dysfunction characteristic for I/RC: compared with wild-type, ROCK-1 -/- hearts showed markedly lower numbers of I/RC-induced α-smooth muscle actin+ fibroblasts and CD34+/ CD45+ fibroblast precursors. Isolated cardiac fibroblasts from ROCK-1-/- mice undergoing I/RC were large and slowly proliferating, similar to fibroblasts isolated from sham-treated hearts. We also performed in vitro assays in which human peripheral blood mononuclear cells (PBMC) migrated through endothelial cells in response to MCP-1. Prior to migration, PBMC were incubated with ROCK-1-targeting small interfering RNA to silence ROCK-1 expression. We found that an 80 reduction of ROCK-1 protein did not inhibit TEM, but significantly reduced the amount of mononuclear cells that differentiated into fibroblasts by >20-fold.ConclusionOur data implicate an important role for ROCK-1 in the differentiation, but not in the TEM of monocytes that mature into cardiac fibroblasts. These cells mediate non-adaptive fibrosis.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Cardiac fibroblasts; Endothelial transmigration; Fibrosis; Monocytes; Rho-associated kinase-1

Sex-related differences among patients undergoing surgical aortic valve replacement—a propensity score matched study - Zierer, Andreas; De Paulis, Ruggero; Bakhtiary, Farhad; Ahmad, Ali El Sayed; Andreas, Martin; Autschbach, Rüdiger; Benedikt, Peter; Binder, Konrad; Bonaros, Nikolaos; Borger, Michael; Bourguignon, Thierry; Canovas, Sergio; et al. (Interdisciplinary CardioVascular and Thoracic Surgery, 2024)
OBJECTIVES: We investigated the sex-related difference in characteristics and 2-year outcomes after surgical aortic valve replacement (SAVR) by propensity-score matching (PSM). METHODS: Data from 2 prospective registries, the INSPIRIS RESILIA Durability Registry (INDURE) and IMPACT, were merged, resulting in a total of 933 patients: 735 males and 253 females undergoing first-time SAVR. The PSM was performed to assess the impact of sex on the SAVR outcomes, yielding 433 males and 243 females with comparable baseline characteristics. RESULTS: Females had a lower body mass index (median 27.1 vs 28.0 kg/m2; P ¼ 0.008), fewer bicuspid valves (52% vs 59%; P ¼ 0.036), higher EuroSCORE II (mean 2.3 vs 1.8%; P < 0.001) and Society of Thoracic Surgeons score (mean 1.6 vs 0.9%; P < 0.001), were more often in New York Heart Association functional class III/IV (47% vs 30%; P < 0.001) and angina Canadian Cardiovascular Society III/IV (8.2% vs 4.4%; P < 0.001), but had a lower rate of myocardial infarction (1.9% vs 5.2%; P ¼ 0.028) compared to males. These differences vanished after PSM, except for the EuroSCORE II and Society of Thoracic Surgeons scores, which were still significantly higher in females. Furthermore, females required smaller valves (median diameter 23.0 vs 25.0 mm, P < 0.001). There were no differences in the length of hospital stay (median 8 days) or intensive care unit stay (median 24 vs 25 hours) between the 2 sexes. At 2 years, post-SAVR outcomes were comparable between males and females, even after PSM. CONCLUSIONS: Despite females presenting with a significantly higher surgical risk profile, 2-year outcomes following SAVR were comparable between males and females.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Aortic stenosis; Sex disparities; Surgical aortic valve replacement

Short-term venous stasis induces fibrinolytic activation but not thrombin formation - Rühl, Heiko; Müller, Jens; Wäschenbach, Jana; Oldenburg, Johannes; Pötzsch, Bernd; Dewald, Oliver (Journal of Atherosclerosis and Thrombosis, 2014)
Aim: Venous stasis is a well-known risk factor for the development of venous thromboembolism. It is likely that stasis increases the risk of thrombosis by inducing hypercoagulability via the hypoxic procoagulant activation of endothelial and mononuclear cells and the accumulation of activated clotting factors. However, increased rates of thrombin formation have not been demonstrated in response to venous stasis in vivo.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Fibrinolysis; Thrombin; Vascular endothelial function

The endocannabinoid-CB2 receptor axis protects the ischemic heart at the early stage of cardiomyopathy - Duerr, Georg D.; Heinemann, Jan C.; Suchan, Georg; Kolobara, Elvis; Wenzel, Daniela; Geisen, Caroline; Matthey, Michaela; Passe-Tietjen, Kristine; Mahmud, Walid; Ghanem, Alexander; Tiemann, Klaus; Alferink, Judith; et al. (Basic Research in Cardiology, 2014)
Ischemic heart disease is associated with inflammation, interstitial fibrosis and ventricular dysfunction prior to the development of heart failure. Endocannabinoids and the cannabinoid receptor CB2 have been claimed to be involved, but their potential role in cardioprotection is not well understood. We therefore explored the role of the cannabinoid receptor CB2 during the initial phase of ischemic cardiomyopathy development prior to the onset of ventricular dysfunction or infarction. Wild type and CB2-deficient mice underwent daily brief, repetitive ischemia and reperfusion (I/R) episodes leading to ischemic cardiomyopathy. The relevance of the endocannabinoid-CB2 receptor axis was underscored by the finding that CB2 was upregulated in ischemic wild type cardiomyocytes and that anandamide level was transiently increased during I/R. CB2-deficient mice showed an increased rate of apoptosis, irreversible loss of cardiomyocytes and persistent left ventricular dysfunction 60 days after the injury, whereas wild type mice presented neither morphological nor functional defects. These defects were due to lack of cardiomyocyte protection mechanisms, as CB2-deficient hearts were in contrast to controls unable to induce switch in myosin heavy chain isoforms, antioxidative enzymes and chemokine CCL2 during repetitive I/R. In addition, a prolonged inflammatory response and adverse myocardial remodeling were found in CB2-deficient hearts because of postponed activation of the M2a macrophage subpopulation. Therefore, the endocannabinoid-CB2 receptor axis plays a key role in cardioprotection during the initial phase of ischemic cardiomyopathy development. © 2014 Springer-Verlag.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Cardiomyopathy; Cardioprotection; Endocannabinoids; Macrophages; Myocardial remodeling

The focal adhesion protein β-parvin controls cardiomyocyte shape and sarcomere assembly in response to mechanical load - Thievessen, Ingo; Suhr, Frank; Vergarajauregui, Silvia; Böttcher, Ralph T.; Brixius, Klara; Rosenberger, Georg; Fleischmann, Bernd K.; Ghanem, Alexander; Krüger, Marcus; Engel, Felix; Fabry, Ben; Bloch, Wilhelm; et al. (Current Biology, 2022)
Physiological and pathological cardiac stress induced by exercise and hypertension, respectively, increase the hemodynamic load for the heart and trigger specific hypertrophic signals in cardiomyocytes leading to adaptive or maladaptive cardiac hypertrophy responses involving a mechanosensitive remodeling of the contractile cytoskeleton. Integrins sense load and have been implicated in cardiac hypertrophy, but how they discriminate between the two types of cardiac stress and translate mechanical loads into specific cytoskeletal signaling pathways is not clear. Here, we report that the focal adhesion protein β-parvin is highly expressed in cardiomyocytes and facilitates the formation of cell protrusions, the serial assembly of newly synthesized sarcomeres, and the hypertrophic growth of neonatal rat ventricular cardiomyocytes (NRVCs) in vitro. In addition, physiological mechanical loading of NRVCs by either the application of cyclic, uni-axial stretch, or culture on physiologically stiff substrates promotes NRVC elongation in a β-parvin-dependent manner, which is achieved by binding of β-parvin to α/β-PIX, which in turn activates Rac1. Importantly, loss-of-function studies in mice also revealed that β-parvin is essential for the exercise-induced cardiac hypertrophy response in vivo. Our results identify β-parvin as a novel mechano-responsive signaling hub in hypertrophic cardiomyocytes that drives cell elongation in response to physiological mechanical loads.
CRIS-Team Scopus Importer:2022-08-05
Keywords: affixin; cardiac hypertrophy; integrin-linked kinase; mechanotransduction; Rac1; sarcomere assembly; β-parvin

The mystery of methylene blue and its role in managing post-cardiac surgery vasoplegic shock - Elbayomi, Mohamed; Dewald, Oliver; Pathare, Presheet; Kondruweit, Markus; Tandler, Rene; Weyand, Michael; Heim, Christian (Annals of Medicine, 2025)
Background: Vasoplegic syndrome is associated with high mortality. Methylene blue (MB) is a guanylate cyclase inhibitor that ameliorates this re-distributive type of shock. This study aims to investigate the outcome in patients who received MB early postoperatively. Methods: 2753 patients who underwent cardiac surgery utilizing cardiopulmonary bypass at our institution in a time interval of two years were identified. The incidence of vasoplegic syndrome was 7.2% (n = 200). Pharmacy records identified 84 patients (group 1, MB group) who received methylene blue and 116 patients (group 2, Control group) who didn’t receive the drug. This single-center retrospective cohort study’s primary outcome was in-hospital mortality. Secondary outcomes were postoperative hemodialysis, serum lactate levels at 24 h postoperatively, and intensive care unit stay length in days. Results: MB patients have a shorter ICU stay as compared to the control group (9 ± 8 days vs. 16 ± 6.9; p-value <.001). In the control group, postoperative hemodialysis was higher (20% in the MB group and 40% in the control group; p-value <.05). At 24 h post-op, the methylene blue group had reduced serum lactate levels (1.8 ± 1.2 vs. 4 ± 1.8 in the control group; p-value <.001). The methylene blue group had a decreased 24-hour norepinephrine dose (1.5 ± 1.2 vs. 2.8 ± 2 in the control group; p-value <.05). In-hospital mortality was not significantly different between the two groups (38% in the MB group vs. 43% in the control group). Conclusion: Early postoperative administration of methylene blue in patients with vasoplegic syndrome shortens intensive care unit stay and contributes to less end-organ damage.
CRIS-Team Scopus Importer:2025-02-14
Keywords: Cardiopulmonary bypass; methylene blue; vasoplegic syndrome

The provision of pediatric cardiac anesthesia services in Germany: current status of structural and personnel organization - Baehner, Torsten; Heinze, Ingo; Mueller, Matthias; Schindler, Ehrenfried; Schirmer, Uwe; Baumgarten, Georg; Hoeft, Andreas; Ellerkmann, Richard K.; Dewald, Oliver (Pediatric Anesthesia, 2017)
Background: Anesthesia for pediatric cardiac surgery requires a high level of expert knowledge. There are currently no recommendations and standards for anesthetic management for congenital cardiac surgery in Germany. Aim: The aim of the present study was to assess the current status of structural and personnel anesthetic standards at pediatric cardiac surgery centers in Germany. Methods: All cardiac surgical centers in Germany were reviewed for an active program for congenital heart surgery. Centers with an active program were invited to respond to an online survey. The questionnaire containing 55 items in 16 categories assessed current practice in pediatric cardiac anesthesia. Results: An active program for pediatric cardiac surgery was identified at 27 centers. The response rate to the survey was 96.3%. A specialized group of anesthesiologists for pediatric cardiac anesthesia was reported from 26 centers (92.3%). The mean size of this group was 4.8 anesthesiologists per center. However, the annual case load of centers and relative annual case load per specialized anesthesiologist varied considerably between 12.5 and 250. Nonanesthesiologists performed sedation and general anesthesia for diagnostic and therapeutic interventions outside the operating theater in children with congenital heart diseases in 24 centers (77%). Although special equipment, for example, pediatric TEE, near-infrared spectroscopy, and devices for mechanical auto transfusion were available in most centers, their routine use was not always part of standard operating procedures. The proposal for mean adequate training in pediatric cardiac anesthesia as estimated by the participating centers was 10.8 months. Conclusion: The present study represents the current structural situation for anesthesia at German pediatric cardiac surgery centers.
CRIS-Team Scopus Importer:2022-05-03
Keywords: congenital heart disease; education; equipment; general anesthesia

Therapy and Outcome of Neonates with Congenital Diaphragmatic Hernia and Congenital Heart Defects Therapie und Outcome von Neugeborenen mit kongenitaler Zwerchfellhernie und angeborenen Herzfehlern - Balks, Julian; Mueller, Andreas; Herberg, Ulrike; Geipel, Annegret; Gembruch, Ulrich; Schroeder, Lukas; Breuer, Johannes; Weidenbach, Michael; Berg, Christoph; Kipfmueller, Florian; Dewald, Oliver (Zeitschrift für Geburtshilfe und Neonatologie, 2021)
The mortality of patients with isolated congenital diaphragmatic hernia (CDH) in specialized centers is 20-40 %. The main factors influencing the outcome are the underlying pulmonary hypoplasia, the resulting pulmonary hypertension and the presence of other malformations. Concomitant malformations such as congenital heart defects occur in around 18 % of all neonates with a diaphragmatic hernia. Serious congenital heart defects such as hypoplastic left heart syndrome occur in approximately 8 % of cases. In a retrospective analysis of the patient collective of our hospital between 01/2012 and 12/2018, the prenatal and postnatal management as well as the outcome of newborns with a combination of congenital heart defects and diaphragmatic hernias were examined. During the study period, 156 newborns with diaphragmatic hernias were treated at our institution. In 10 patients (6.4 %) there was also a severe, and in 11 patients (7.1 %) a moderate heart defect. 6/21 patients died during their hospital stay, 3 of them on the first day of life. There was a significantly lower mortality in patients with diaphragmatic hernia and moderate heart defects compared to severe heart defects (9 vs. 50 %). The mortality in children with a univentricular heart was particularly high. Despite a significantly reduced prognosis for the combination of congenital heart defects and diaphragmatic hernia, generally a poor prognosis does not have to be expected. A curative approach can be achieved in specialized centers.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Congenital diaphragmatic hernia; congenital heart defect; extracorporeal membrane oxygenation (ECMO); lung hypoplasia; pulmonary hypertension

The value of perioperative biomarker release for the assessment of myocardial injury or infarction in cardiac surgery - Schneider, Ulrich; Mukharyamov, Murat; Beyersdorf, Friedhelm; Dewald, Oliver; Liebold, Andreas; Gaudino, Mario; Fremes, Stephen; Doenst, Torsten (European Journal of Cardio-Thoracic Surgery, 2022)
OBJECTIVES: Cardiac biomarkers are indicators of irreversible cell damage. Current myocardial infarction (MI) definitions require concomitant clinical characteristics. For perioperative MI, a correlation of biomarker elevations and mortality has been suggested. Definitions emerged relying on cardiac biomarker release only. This approach is questionable as several clinical and experimental scenarios exist where relevant biomarker release can occur apart from MI. METHODS: We reviewed the clinical and basic science literature and revealed important aspects regarding the use and interpretation of cardiac biomarker release with special focus on their interpretation in the perioperative setting. RESULTS: Ischaemic biomarkers may be released without cell death in multiple conditions, such as after endurance runs in athletes, temporary inotropic stimulation in animal models and flow variations in in vitro cell models. In addition, access through atrial tissue during cannulation or concomitant valve procedures adds sources of enzyme release that may not be related to ventricular ischaemia (i.e. MI). Such non-cell death-related mechanisms may explain the lack of poor correlations of enzyme release and long-term outcomes in recent trials. In addition, the 3 main biomarkers, troponin T, I and creatine kinase myocardial band, differ in their release kinetics, which may differentially trigger MI events in trial patients. CONCLUSIONS: The identification of irreversible myocardial injury in cardiac surgery based only on biomarker release is unreliable. Cell death- and non-cell death-related mechanisms create a mix in the perioperative setting that requires additional markers for proper identification of MI. In addition, the 3 most common ischaemic biomarkers display different release kinetics adding to the confusion. We review the topic.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Biomarker; Myocardial infarction

Timely extracorporeal membrane oxygenation assist reduces mortality after bypass surgery in patients with acute myocardial infarction - Hamiko, Marwan; Slottosch, Ingo; Scherner, Max; Gestrich, Christopher; Wahlers, Thorsten; Putensen, Christian; Mellert, Fritz; Treede, Hendrik; Duerr, Georg Daniel; Dewald, Oliver (Journal of Cardiac Surgery, 2019)
Background: Patients with acute myocardial infarction (AMI) are at high risk when undergoing emergency coronary artery bypass graft (CABG)-surgery. Their outcome remains poor despite increased use of extracorporeal membrane oxygenation (ECMO). We investigated the impact of timing for perioperative ECMO-support in these patients. Methods: In this retrospective double-center study, we evaluated 201 patients with AMI undergoing CABG, dividing them into the following groups: No-ECMO (n = 101), preoperative ECMO (pre-ECMO, n = 6), intraoperative ECMO (ECC-ECMO, n = 67), and postoperative ECMO (post-ECMO, n = 27). We evaluated the impact of ECMO timing on postoperative mortality, organ function, and length of stay, comparing these to predicted outcome using different risk-scores. Results: Post-ECMO patients showed lowest 30-day-survival (40.7%), while earlier ECMO-start was associated with better outcome (50.7% in extracorporeal circulation [ECC]-ECMO and 66.7% in pre-ECMO patients). On admission, only pre-ECMO and ECC-ECMO patients showed higher surgery- and intensive-care-unit (ICU)-related risk-scores. In pre- and ECC-ECMO patients, the first significant increase in lactate-levels (>4 mmol/L) was observed preoperatively, while this occurred 1 hour postoperatively in post-ECMO patients. Bilirubin was increased in all patients, decreasing after 3 and 12 days in pre- and ECC-ECMO patients, respectively, but only after 18 days in post-ECMO patients. Multiple ICU risk-scores did not discriminate survival-probability correctly. Only the ECMO-related survival after veno-arterial-ECMO-score correctly predicted the significantly lower survival in post-ECMO patients. Conclusion: Our study shows that timely ECMO-support is associated with earlier bilirubin-downtrend and higher survival in patients with AMI after CABG. Lactate-increase greater than 4 mmol/L seems to be a helpful threshold to trigger the timely onset of ECMO-therapy, providing better survival.
CRIS-Team Scopus Importer:2022-05-03
Keywords: acute myocardial infarction; cardiogenic shock; circulatory support; coronary artery bypass graft; extracorporeal membrane oxygenation

Ultrasound-Mediated Stimulation of Microbubbles after Acute Myocardial Infarction and Reperfusion Ameliorates Left-Ventricular Remodelling in Mice via Improvement of Borderzone Vascularization - Doerner, Jonas; Struck, Rafael; Zimmer, Sebastian; Peigney, Christine; Duerr, Georg Daniel; Dewald, Oliver; Kim, Se-Chan; Malan, Daniela; Bettinger, Thierry; Nickenig, Georg; Ghanem, Alexander (PLoS ONE, 2013)
Aims: Post-infarction remodelling (PIR) determines left-ventricular (LV) function and prognosis after myocardial infarction. The aim of this study was to evaluate transthoracic ultrasound-mediated microbubble stimulation (UMS) as a novel gene- and cell-free therapeutic option after acute myocardial infarction and reperfusion (AMI/R) in mice. Methods and Results: For myocardial delivery of UMS, a novel therapeutic ultrasound-system (TIPS, Philips Medical) and commercially available microbubbles (BR1, Bracco Suisse SA) were utilized in a closed-chest mouse model. UMS was performed as myocardial post-conditioning (PC) on day four after 30 minutes of coronary occlusion and reperfusion. LV-morphology, as well as global and regional function were measured repeatedly with reconstructive 3-dimensional echocardiography applying an additional low-dose dobutamine protocol after two weeks. Scar size was quantified by means of histomorphometry. A total of 41 mice were investigated; 17 received PC with UMS. Mean ejection fraction (EF) prior UMS was similar in both groups 53%±10 (w/o UMS) and 53%±14 (UMS, p = 0.5), reflecting comparable myocardial mass at risk 17%±8 (w/o UMS), 16%±13 (UMS, p = 0.5). Two weeks after AMI/R, mice undergoing UMS demonstrated significantly better global LV-function (EF = 53%±7) as compared to the group without PC (EF = 39%±11, p<0.01). The fraction of akinetic myocardial mass was significantly lower among mice undergoing UMS after AMI/R [27%±10 (w/o UMS), 13%±8 (UMS), p<0.001)]. Our experiments showed a fast onset of transient, UMS-induced upregulation of vascular-endothelial and insulin-like growth factor (VEGF-a, IGF-1), as well as caveolin-3 (Cav-3). The mice undergoing PC with UMS after AMI/R showed a significantly lower scar size. In addition, the microvascular density was significantly higher in the borderzone of UMS-treated animals. Conclusion: UMS following AMI/R ameliorates PIR in mice via up-regulation of VEGF-a, IGF-1 and Cav-3, and consecutive improvement of myocardial borderzone vascularization. © 2013 Dörner et al.
CRIS-Team Scopus Importer:2022-05-03